RLX-2 ameliorates post-traumatic joint contracture by inhibiting the cGAS-STING signaling pathway - Jian-Jun Chen; Quan-Bing Zhang; Yan Wang; Chen Chen; Yi Liu; Zun-Yu Du; Xiu-Li Kan; Han Xiao; Xue-Ming Li; Run Zhang; De-Ting Zhu; Xian-Liang Rao; et al. (Tissue and Cell, 2027)

Nitrogen-doped porous carbon from sucrose-polyaniline precursor co-processing: high CO2 adsorption performance and cyclic stability - Li Zhao; Run Zhang; Yong-sheng Ma; Zhong-hao Wu; Qi Niu; Xin-hua Yuan; Xin-yue Zhou; Kai Li; Qiang Lu (Biomass and Bioenergy, 2027)

Genome-wide identification and evolution of the RCP gene family in soybean uncovers stress-responsive candidates - Xiaoli Guan; Run Yuan; Ao Shen; Yanhong Wang; Yuanmeng Yu; Liying Zou; Yuming Yang; Jinyu Zhang; Zhongwen Huang; Li Wang (Functional & Integrative Genomics, 2026)

Cross domain fault diagnosis of small modular reactor using sample synthesis and transfer learning with attention mechanism - Run Luo; Xiangcheng Pan; Yadong Li; Yang Liu; Hongtao Wan; Shun Hu; Tao Yu; Chao Xie (Annals of Nuclear Energy, 2026)

Sphagnum trait-mediated service function in response to phosphorus and nitrogen dynamics on the karst plateau - Chengyi Li; Run Liu; Mingzhu He; Jiachen Shen; Zhaohui Zhang; Qimei Wu; Dengfu Wang; Hong Sun (Forest Ecology and Management, 2026)

Safety, immunogenicity, and broad-spectrum protective efficacy of a naturally attenuated GCRV-II strain against viral and bacterial challenges in grass carp - Dingzhe Zou; Yifei Li; Jie Zhou; Wangqian Xu; Ying Tian; Run Yang; Yujie Gu; Xiangyu Tian; Yucheng Lin; Jiping Zhang; Weiwei Zeng (Fish & Shellfish Immunology, 2026)

Lignin-first depolymerization of softwood over a NiCu/TiO2 catalyst for the sustainable production of dihydroconiferyl alcohol - Peng Zhu; Yu-Xin Zhang; Qiang Wang; Guo-Hui Cheng; Jun-Li Ren; Ling-Ping Xiao; Run-Cang Sun (Bioresource Technology, 2026)

Sp1 induces autophagic in epithelial ovarian cancer through inhibition of the PI3K/AKT/mTOR pathway - Yushuang Zheng; Xu Xu; Zheyu Lu; Wangzhi Li; Lu Wang; Run Luo; Keqi Xu; Fan Wang (Tissue and Cell, 2026)

Improving ENSO hindcast skill by adjusting the mean background state in a coupled general circulation model (CAS-ESM2.0) - Guixian Li; Guangqing Zhou; Jiangbo Jin; Run Guo; Yuyuan Zhang (Ocean Modelling, 2026)

Effect of zero-valent iron and its oxidation products as alternative electron donor on the partial denitrification performance - Zi-Yue Li; Run-Mei Li; Jia-Min Zhou; Yi-Nan Zhang; Zhe Wang; Yao Zou; Ren-Cun Jin; Qian-Qian Zhang (Journal of Environmental Chemical Engineering, 2026)

Molecular adsorption and infrared-driven photocatalytic performance of nitrogen-defective g-C3N4 regulated by Ti doping and oxygen atmosphere treatment - Ziqian Zhang; Ziheng Li; Yu Wang; Yixuan Chen; Yitian Wang; Yuyang Guo; Run Liu; Guancheng Wang; Xingyu Gao; Youyu Pang (Journal of Environmental Chemical Engineering, 2026)

The unintentional adverse effect of Fe3 + on trimethoprim adsorption at environmentally relevant concentration by extracellular polymeric substances - You Ma; Tian-Yu Li; Zi-Yi Fan; Han Meng; Guo-Xiang Wang; Fang Fang; Yu-Dong Chen; Run-Ze Xu; Wen-Ming Xie (Journal of Environmental Chemical Engineering, 2026)

Ex-situ catalytic microwave-assisted gasification of sewage sludge over Ni-modified MIL-100 (Fe) derived catalysts: Tar reforming for hydrogen-rich syngas - Mingtao Hu; Huiwen Wu; Wenyi Deng; Lingyu Tai; Xuerong Zheng; Weihao Li; Yaxin Su; Run Xu (Journal of Environmental Chemical Engineering, 2026)

Experimental investigation on adiabatic two-phase frictional pressure drop of R32, R1234ze(E), and their mixtures in a horizontal minichannel - Na Liu; Yeyi Liu; Hao Ji; Dezheng Sun; Run Li; Chuandian Dong; Huan Lin (International Journal of Refrigeration, 2026)

Revealing the dominant role of pectin in softening texture and enhancing drying behaviors of grapes after cold plasma pretreatment - An-An Zhang; Fan Yang; Ming-Qiang Xu; Wei-Peng Zhang; Jin-Run Li; Hai-Bin Yang; Jing-Shou Zhang; Wei-Qiao Lv; Hong-Wei Xiao (Food Research International, 2026)

Species composition and community assembly characteristics of biological soil crusts in degraded karst ecosystems of Guizhou, China - Jinru Liu; Xin Zhao; Minghao Deng; Fugui Zhang; Qimei Wu; Run Liu; Mingzhong Long; Xiaona Li (Plant Biosystems, 2026)

Study on upper bound solution of anti-overturning bearing capacity of pile-bucket composite foundation in sand - Guang-si Chen; Rui Zhou; Le Wang; Run Liu; Tian-liang Li (Marine Georesources & Geotechnology, 2026)

Dead pine tree detection using an iterative semi-supervised framework integrating expert annotation and active learning - Xiaolin Li; Run Yu; Yu Qiu; Jianlong Luo; Xiaojian Lu; Shiguo Huang; Songqing Wu; Feiping Zhang (Computers and Electronics in Agriculture, 2026)

The lnc40545-miR-965-CYP307A1 regulation pathway mediates imidacloprid resistance in Rhopalosiphum padi (L.) - Yong-Po Lv; Ren-Jie Li; Yu-Tai Jiang; Bai-Zhong Zhang; Yu-Yang Peng; Yong Sun; Dong-Mei Chen; Fan-Bin Kong; Run-Qiang Liu; Hai-Hong Gu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Preferential Impacts of the Western-Pacific Subtropical High and Australian High on the Indian Ocean Dipole Phases - Zhanglin Li; Hong-Li Ren; Minghong Liu; Run Wang (Advances in Atmospheric Sciences, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

Magnetotelluric strong interference detection and signal reconstruction via recurrence quantification analysis and deep learning - Pei-Lin Zhang; Jia-Qing Wang; Jian-Nan Song; Run-Lin Luo; Ya-Nan Li; Chang-Wei Li (Applied Geophysics, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Mechanistic insights into triclocarban-induced skin barrier disruption via integrating imaging localization, multi-omics, and network toxicology - Jingwen Zheng; Run Guo; Rong Zhang; Xinyu Liu; Rouyue Guo; Haozheng Li; Juntong Wei; Yuxin Zheng; Hongna Zhang (Environmental Pollution, 2026)

One-step fabrication of porous carbon via molten salt-assisted pyrolysis and evaluation of its CO2 adsorption performance - Li Zhao; Run Zhang; Ting Huang; Ding-wang Qiao; Qi Niu; Ze-jun Luo; Kai Li; Qiang Lu (Biomass and Bioenergy, 2026)

RDO3 REPRESSOR 27, a new MED25 allele, regulates seed dormancy dependent on DOG1 and ABA pathways in Arabidopsis - Yue Yang; Xiao-Ying Li; Run Ding; Hong Cao; Yongxiu Liu; Yu Li (Planta, 2026)

Biochemical and multi-omics analyses reveal skeletal muscle adaptation to chronic low-salinity stress of marine medaka (Oryzias melastigma) - Tian-Hong Chen; Qing-Hao Zhan; Xiao-Yu Zeng; Ning-Ning Ma; Qi-Liang Li; Run-Jie Jin; Jia-Lang Zheng; Qing-Ling Zhu (Fish Physiology and Biochemistry, 2026)

A Musculoskeletal-Finite Element Study of Knee Joint Loading and Cartilage Mechanics in Children with Cerebral Palsy - Dongfei Huo; Run Lin; Junyan Li; Timothy P. Holsgrove; Dominic Farris; Dong Wang; Xijin Hua (Annals of Biomedical Engineering, 2026)
Purpose Cerebral palsy (CP) is typically associated with abnormal gait that may alter knee joint loading and accelerate joint degeneration. We developed an integrated musculoskeletal-finite element (MSK-FE) framework to quantify differences in knee joint biomechanics between children with CP and typically developing (TD) peers. Methods Gait data from 13 children (TD, n = 5; hemiplegia [HP], n = 4; diplegia [DP], n = 4) were analyzed using OpenSim to obtain knee kinematics and compressive knee joint reaction forces (KJRFs). These were applied to scaled 3D FE knee models, incorporating biphasic cartilage, menisci, and ligaments, at the first force peak, mid-stance, and second force peak to evaluate cartilage pressures. Results Compared with TD, both CP subtypes (HP and DP) exhibited greater knee flexion throughout the gait cycle, except for the affected limb in HP (HP A ), which showed reduced flexion during the stance phase. Peak KJRFs over the gait cycle were slightly higher in DP and HP A than in TD, whereas the unaffected limb in HP (HP UA ) generated the highest peak KJRFs among all groups, indicating compensatory overloading of the unaffected limb in HP. Correspondingly, FE analysis showed that peak cartilage contact pressures in the HP cohorts were significantly higher than in DP and TD, while pressures in DP were slightly higher than in TD over the gait cycle. The HP UA showed the highest contact pressures among all groups. Conclusion The MSK-FE framework quantified knee loading and cartilage contact pressure patterns in children with CP. These preliminary findings highlight subtype- and limb-specific gait-loading patterns and provide a mechanistic basis for future larger-scale and longitudinal investigations.

Assessing climate-driven shifts in mariculture across coastal China: Implications for sustainable management and conservation - Yanwei Sun; Ying Li; Run Wang; Xuewei Hou; Renfeng Ma (Regional Studies in Marine Science, 2026)

Undescribed and nephroprotective diterpenoids from Daphne genkwa - Hong-Bo Ye; Xian-Run Wu; Li Wang; Hui-Zhen Peng; Yu Duan; Yun-Li Zhao; Min Ye; Xiao-Dong Luo (Phytochemistry, 2026)

Extent of soil disturbance and spatial strength degradation induced by spudcan penetration and extraction in clay - Cheng-feng Li; Rui Zhou; Run Liu; Hai-yang Zhang; Peng-cheng Ma (Ocean Engineering, 2026)

Insights into the regulatory role of pulsed electric field-induced ROS burst in metabolite changes during potato processing: Integrated transcriptomic and metabolomic analysis - Renjie Zhao; Qiannan Liu; Jing Li; Run Shi; Ruixuan Zhao; Honghai Hu (Food Chemistry, 2026)

Characteristics of the radar bright band observed over a high-altitude lake - Run Han; Yingying Chen; Xiaoyan Ling; Kun Yang; Xin Li; Junbo Wang; Changhui Zhan; Xu Zhou; Ming Chen (Atmospheric Research, 2026)

Skeleton-guided 3D digitization standardizes complex trait phenotyping and supports reproducible locus discovery in cucumber - Tingting Qian; Wanyi Liu; Yue Chen; Xiuguo Zheng; Linyi Li; Run Cai; Junsong Pan; Haifan Wen; Jian Pan (Theoretical and Applied Genetics, 2026)

Soil type drives the effects of biodegradable microplastics on plant growth and litter decomposition in karst regions - Run Liu; Chengyi Li; Qimei Wu; Dengfu Wang; Jiachen Shen (Applied Soil Ecology, 2026)

Per- and polyfluoroalkyl substances in food contact materials: Migration, health risks and sustainable alternatives - Run Li; Shensheng Xiao; Jiayong Hu; Qiao Wang; Jingguang Li; Min Fang; Nannan Qiu; Xin Liu; Yongning Wu (Trends in Food Science & Technology, 2026)

High-thermopower ionic thermoelectric hydrogel with gradient immobilization of anions by polypyrrole - Zhou Li; Wenzhuo Zhao; Shouze Li; Dongyan Xu; Wonjoon Choi; Run Hu (Chemical Engineering Journal, 2026)

Galacto-oligosaccharides enrich galactosidase-encoded rather than all Lachnospiraceae bacteria to redress abnormal gut microbiota and lipid metabolism in pregnancy - Rujun Wei; Jiyun Long; Haoxue Xia; Yanni Sun; Lin Zhang; Xiaoqing Li; Hongping Zhang; Run Wang; Shengtao Gao; Yunwei Chen; Yun Gu; Xiaoya Wang; et al. (Science China Life Sciences, 2026)

Integrating elite selection and micropropagation: a production line for early-stage domestication of Vaccinium bracteatum - Chuizheng Xia; Muhammad Junaid Rao; Ying Wu; Yuanyuan Li; Xuefeng Wang; Weicong Hong; Mengxue Wang; Yihong Jin; Jiani Zhu; Xuan Yu; Haidi Yuan; Jiao Wang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

UCHL1-mediated deubiquitination of GLOD4 regulates mitochondrial homeostasis and PTC malignant progression via GLO1 - Lei Cai; Li-Yuan Qian; Wei Wu; Bo-Ni Ding; Zi-Run Luo; Juan Du (Molecular and Cellular Biochemistry, 2026)

First isolation and identification of a rhabdovirus from bluegill sunfish (Lepomis macrochirus) - Haiyue Chen; Wangqian Xu; Dingzhe Zou; Baozhou Wu; Shuguang Hao; Huajia Yao; Jie Zhou; Ying Tian; Yifei Li; Run Yang; Yujie Gu; Yu Liu; et al. (Aquaculture, 2026)

Uncertainty quantification and physical information learning for safe measurement of resonant flowmeters in multiphase flow: A Bayesian approach with physically-constrained residual injection - Ziwei Yang; Haibo Liang; Run Jiang; Mingyang Liu; Deshen Li; Jie Liu; Jingwen Hu (Process Safety and Environmental Protection, 2026)

Molecular epidemiology reveals co-circulation of five Anaplasma species with zoonotic potential in sheep and goats from Henan province, China - Jia-Run Yang; Wei-Hao Tan; Jie-Yue Liang; Jing-Rong Li; Yu-Ru Cao; Wan-Yu Li; Jian-Wei Shao (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Co-assembled organic phosphorescent crystals with ultralong phosphorescence in high-temperature and water environment - Bin Li; Ziyi Lu; Wensheng Xu; Run Wang; Jiang Liu; Linshuo Jiang; Yin Xiao; Jianchao Ma; Yang Li; Xilong Yan; Bowei Wang; Ligong Chen (Chemical Engineering Journal, 2026)

Defect-passivated Te-doped Cs2HfCl6 perovskite microcrystals with high efficiency and robust stability for X-ray imaging - Yanqing Zu; Run Gan; Lixia Jing; Bing Yang; Binglin Zeng; Liru Yuan; Peitao Liu; Xiaodong Li; Ailing Feng; Lei Zhou (Chemical Engineering Journal, 2026)

Tissue Tropism and Pathogenesis of LMBV in Largemouth Bass: A Comparative Study of Injection and Immersion Infection Models - Tianmei Hu; Dingzhe Zou; Baozhou Wu; Haiyue Chen; Shuguang Hao; Ying Tian; Wangqian Xu; Yifei Li; Jie Zhou; Run Yang; Jiping Zhang; Yu Liu; et al. (Journal of Fish Diseases, 2026)
Largemouth bass ranavirus (LMBV) poses a significant threat to the aquaculture industry by causing severe systemic disease and substantial economic losses. This study investigates the tissue distribution, pathological damage, and host response following LMBV‐GD1909 infection using two infection models: experimental injection and simulated natural immersion. In the injection model, infected fish exhibited clinical signs, including skin ulcers, haemorrhaging at fin bases, body darkening and organ swelling. Histopathological analysis revealed extensive multi‐organ damage, particularly in the liver, spleen, and kidney, characterised by necrosis, haemorrhage, vacuolar degeneration and inflammatory infiltration. Haematological and serum biochemical analyses indicated significant alterations in key parameters, including elevated WBC, RBC and GLU levels, and reduced PLT, TP and LDH levels, reflecting systemic physiological disruption. Viral dynamics analysis demonstrated the pantropic nature of LMBV, with rapid dissemination to multiple tissues post‐injection. The liver and spleen were identified as primary target organs, showing the highest viral loads and most severe pathology, indicating a direct correlation between viral load and organ dysfunction. In the immersion model, simulating natural infection, the gills and skin displayed the highest viral loads initially, identifying them as the major entry portals. The gills also served as a key site for viral replication, with a clear gradient of viral spread from external to internal tissues observed over time. This study comprehensively elucidates the tissue tropism, dissemination pathways, and pathological impact of LMBV, providing critical insights for developing targeted prevention and control strategies against LMBV.

Experimental study on spray-induced fouling on the outer surface of heat exchangers - Liansheng Liu; Hangkai Liu; Yuhui Li; Run Sun; Xuanchen Liu (Process Safety and Environmental Protection, 2026)

Sanxiapeptin inhibits Penicillium digitatum by affecting cell surface and ROS accumulation - Xiaoxuan Bai; Jing Li; Renqing Xiong; Siyu Liu; Run Liu; Gaojie Zhu; Yingping Huang; Shiping Liu (Postharvest Biology and Technology, 2026)

Biogas slurry substitution for chemical fertilizer under fertigation enhances soil fertility and maize yield sustainability: A meta-analysis - Yue Jiang; Bin Shi; Run Xue; Hong Li; Bingyu Li; Luya Wang; Nuo Li (Journal of Environmental Management, 2026)

Nondecomposer-mediated nutrient transfer in soils: experimental evidence from Drosophila - Yunchao Luo; Run Liu; Tingting Cao; Jiayue Zhang; Mengna Zhao; Ke Li; Zunian Ran; Lin Wang; Xingjun Tian (Applied Soil Ecology, 2026)

DrPISA: Deep eutectic solvent-assisted reverse proteome-integrated solubility alteration for high-sensitivity drug target identification - Liu Yang; Tian-Bo Ma; Chen-Wan Guo; Run-Bo Yu; Ping Li; Hua Yang; Wen Gao (Analytica Chimica Acta, 2026)

Effects of Light Intensity and Photoperiod on the Feeding Behavior of Rainbow Trout Oncorhynchus mykiss (Walbaum, 1792) - Xiao Liu; Liuyi Huang; Qiqing Liu; Run Wang; Bo Liu; Zhaomin Li; Yacai Song; Ziyi Huang (Fishes, 2026)
Light is a critical factor influencing fish behavior, yet the low-light conditions in deep-sea cages may impair feeding in visual species like rainbow trout Oncorhynchus mykiss (Walbaum, 1792). This study investigated the effects of light intensity and photoperiod on the feeding behavior of rainbow trout. Using green light, a factorial design tested three light intensities (10, 100, and 1000 lx) and three photoperiods (8L:16D, 16L:8D, and 24L:0D), alongside a complete darkness control (0 lx and 0L:24D). Key behavioral parameters during feeding were quantified via video analysis. The results showed significant main and interactive effects of light intensity and photoperiod on feeding behaviors. Feeding activity was substantially suppressed under continuous darkness. On the initial experimental day, exploratory movement was greatest under 10 lx and 8L:16D. Following 50 days of exposure, fish in light groups exhibited more focused swimming trajectories near the feeding point, indicating behavioral adaptation and spatial learning. Correlation analyses suggested a strategic shift from broad exploration to precise, efficient localization over time. In conclusion, specific lighting conditions, notably low intensity under a regular photoperiod, promote efficient feeding behavior in rainbow trout, whereas darkness or extreme light regimens are inhibitory. These findings reveal adaptive behavioral plasticity in this species and provide a scientific basis for optimizing light management in offshore salmonid aquaculture.

Transcriptomic profiling reveals that NSDV exploits autophagy as a proviral mechanism to enhance viral replication - Xue-Lian Zhang; Xiao-Wen Li; Wei-Hao Tan; Jia-Run Yang; Jie-Yue Liang; Jian-Wei Shao (Veterinary Microbiology, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Research progress on co-processing of MSWI FA using high-temperature industrial waste heat - Hongzhi Ma; Congqi Zhang; Hao Wang; Run Shi; Hao Li; Yan Zhang; Xuguang Wang; Wei Su; Yi Xing; Lei Zheng (Process Safety and Environmental Protection, 2026)

Variable erosion depth in the Chinese Loess Plateau driven by human activities: Evidence from lacustrine uranium comminution ages - Run Zhang; Laifeng Li; David William Hedding; Dejun Wan (Quaternary Science Reviews, 2026)

Experimental investigation on adiabatic two-phase frictional pressure drop of R290, R600a, and their mixtures in a horizontal minichannel - Na Liu; Hao Ji; Yeyi Liu; Run Li; Dezheng Sun; Qian Zhao; Jianxiang Guo (International Journal of Refrigeration, 2026)

Corrosion behavior and biocompatibility of MgZnP@PDA coatings on biodegradable Zn2Cu alloy - Rui Yue; Suqin Wang; Yusong Pan; Yusheng Zuo; Xiancai Meng; Gaozhi Jia; Xiuling Lin; Run Huang; Shaoding Sheng; Lingyu Li (Chemical Engineering Journal, 2026)

Kerogen-driven synergistic interactions in oil shale and microplastics co-pyrolysis: mechanistic insights into product distribution and oil upgrading - Shuai Li; Erfeng Hu; Guangwen Xu; Jianglong Yu; Haifeng Gong; Zuohua Liu; Guocan Zheng; Run Dong; Fan Xu (Chemical Engineering Journal, 2026)

Esterified starch-anthocyanin composite particles synergizing with ZnCDs to construct intelligent porous films: Long-term maintenance and real-time monitoring of shrimp freshness - Run Ji; Wentao Zhang; Lepei Wang; Xiquan Li; Xinhua Zhang; Fengxian Qin; Feiwu Li; Xiuling Zhang; Tiezhu Li (Chemical Engineering Journal, 2026)

The role of moss crusts in soil organic carbon accumulation and microbial ecological regulation in post-fire karst areas of Guizhou, China - Run Liu; Chengyi Li; Qimei Wu; Dengfu Wang; Zhaohui Zhang; Jiachen Shen (CATENA, 2026)

Insights into the effect of biochar on single-stage partial denitrification/anaerobic ammonium oxidation process: Nitrogen removal performance and mechanism - Run-Mei Li; Zi-Yue Li; Jia-Min Zhou; Yi-Nan Zhang; Zhe Whang; Yao Zou; Ren-Cun Jin; Qian-Qian Zhang (Bioresource Technology, 2026)

A novel multi-modal signals dynamic assessment method of idiopathic scoliosis patients for rehabilitation - Mingjie Dong; Chengyin Wang; Yinbo Chen; Yuechuan Zhang; Zhuosong Bai; Shuo Wang; Jianguo Zhang; Run Ji; Jianfeng Li; Bin Fang; Qianyu Zhuang (Medical & Biological Engineering & Computing, 2026)

Investigating the failure mechanism of a landslide triggered by the combined effects of excavation and rainfalls through numerical approaches - Shu-wei Sun; Xin-yu Fu; Yuan Li; Qiang Wen; Run-jie Gong (Landslides, 2026)

Research on Intelligent Identification of Dike Hidden Hazards Based on GprMax Forward Modeling and YOLOv11 Deep Learning: A Case Study of Wenzaobang River in Shanghai - Fu-yu Jiang; Run Han; Li-kun Gao; Jiong Ni; Jun-kai Yu; Xiao-yu Xu (Applied Geophysics, 2026)

Failure Behavior and Energy Evolution of Granite Containing Pre-existing Fissures Characterized by AE and DIC - Run-ze Zhang; Chuan-xin Rong; Bin Wang; Hua-qiao Xu; Yan-zhe Li; Yang Wang (Applied Geophysics, 2026)

Simulation-to-Reality transfer learning with UAV-based imagery for forest inventory attribute prediction - Qing Guo; Linyuan Li; Run Yu; Zhuangzhuang Zhang; Huaguo Huang (Computers and Electronics in Agriculture, 2026)

Effects of light intensity and photoperiod on the growth performance, stress response, and metabolism of steelhead trout (Oncorhynchus mykiss) - Xiao Liu; Liuyi Huang; Qiqing Liu; Run Wang; Bo Liu; Zhaomin Li; Yacai Song; Ziyi Huang; Chunwei Bi; Xinxing You (Aquaculture, 2026)

Distributed proximal primal–dual splitting for coupled constrained optimization over directed unbalanced networks - Run Tang; Huaqing Li; Dawen Xia; Liang Ran; Jun Li; Wei Zhu (Swarm and Evolutionary Computation, 2026)

Study on the dynamic response and system reliability of curved beam bridge under multi-dimensional non-uniform random earthquake excitation - Xi-mei Li; Peng-hui Fan; Wan-run Li; Yong-feng Du (Soil Dynamics and Earthquake Engineering, 2026)

Short-, medium-, and long-chain chlorinated paraffins in sediments from the Pearl River Delta, China: Occurrence, sources, and risks - Fei-Xiang Xie; Yu-Fang Huang; Yong-Hong Zhang; Ya-Hui Xue; Run-Lin Chen; Xiao-Mei Huang; Hong-De Shi; Jia-Hui Huang; Hui-Ru Li (Science of The Total Environment, 2026)

An unprecedented alternariol-zinnol hybrid and six undescribed zinnol derivatives from the phytopathogen Alternaria solani and their cytotoxic activities - Ming Hu; Run-Cheng Yan; Qiao-Ling Wei; Jiang-Li Su; Bi-Juan Yang; Wen-Chao Tu; Gan-Peng Li; Xing-De Wu (Phytochemistry, 2026)

Unraveling the catalytic/adsorptive roles of powdered activated carbon in iodide removal by Mn(VII) oxidation - Run Huang; Chaoting Guan; Juan Li; Yi Yang; Yongze Liu; Jin Jiang (Journal of Hazardous Materials, 2026)

Mercury isotope perspectives on vegetation-enhanced nickel mobilization and migration during laterite formation - Ruo-Lin Liu; Martin Yan Hei Li; Run-Sheng Yin; Mei-Fu Zhou; Jun-Hong Zhao (Geochimica et Cosmochimica Acta, 2026)

Numerical investigation on combustion behavior of an X-type rotary engine: Impact of hydrogen enrichment and engine speed - Run Zou; Lei Zhang; Ting Hou; Yanhong Zhou; Wei Yang; Lijun Lei; Feng Li (Fuel, 2026)

Mountain laurel-like FeCo alloy decorated nitrogen-doped reduced graphene oxide composites for broadband and high-efficiency microwave absorption - Ruiwen Shu; Yongmei Li; Run Huang; Konghu Tian; Xiaoli Ji (Chemical Engineering Journal, 2026)

Mitigation of adverse effects of calcium on struvite biomineralization for phosphorus recovery - Xingtong Chen; Yongyun Li; Yifei Ma; Bing Li; Yihe Qin; Xiaoman Li; Run Yuan; Jingjing Chen; Suran Huang; Han Li; Haiming Huang (Bioresource Technology, 2026)

Deciphering the quorum sensing driven microbial coordination underlying anaerobic digester foaming - Wenjie Ye; Lei Li; Yongli Liu; Run Guan; Jiaqi Huang; Yun Xu; Xuya Peng; Xiaoming Wang (Water Research, 2026)

Pyrogenic carbon-stimulated nitrate-dependent anaerobic methane oxidation: insights into redox activity and conductivity in anaerobic methanotrophic archaea metabolism and microbial dynamics - Fangrui Cai; Yu Wang; Mengying Xie; Guanbin Li; Suicao Wang; Venea Dara Daygon; Dihua Tian; Gaofeng Ni; Xiang Liu; Run Zhang; Lirong Lei; Zhiguo Yuan; et al. (Water Research, 2026)

Alstoniaschines A‒I, nine undescribed alkaloids from Alstonia scholaris and their potential medicinal effects on diabetic nephropathy - Wen-Jie Sun; Shi-Shi Qin; Xian-Run Wu; Yun-Li Zhao; Xu-Jie Qin; Xiao-Dong Luo (Phytochemistry, 2026)

Autophagy, ROS, and their interplay in plant adaptive responses - Chi Zhang; Song-Qi Li; Pengwei Jing; Run-Xin Wu; Yu-Qing Ma; Ji-Xiao Wu; Ru-Feng Song; Wen-Cheng Liu (Journal of Plant Physiology, 2026)

The adaptation of prehistoric human activities to environmental changes recorded in a lake core on the Tibetan Plateau - Cunlin Li; Liping Zhu; Qingfeng Ma; Jianting Ju; Marco A. Aquino-López; Qiangqiang Kou; Shuyu Pang; Run Zhang; Minghui Li; Xinmiao Lü; Junbo Wang (Global and Planetary Change, 2026)

Effect of air frying, oven baking, pan frying, and deep frying on flavor profile and acrylamide formation in reheated hash browns - Run Shi; Qiqi Mi; Renjie Zhao; Qiannan Liu; Jing Li; Wei Liu; Ruixuan Zhao; Honghai Hu (Food Chemistry, 2026)

Mechanistic insight into curcumin-induced conjugative plasmid transfer acceleration: Role of intracellular arginine uptake - Min-ge Wang; Kai-di Liu; Wen-jie Jin; Run-bo Li; Jun-qi Liu; Liang-xing Fang; Jian Sun; Xiao-ping Liao (Food Microbiology, 2026)

Solubility characteristics and recovery study of 4-tert-Butyl-2-(α-methylbenzyl) phenol (t-BAMBP) in cesium and rubidium extraction systems - Boren Tan; Yazhou Li; Zichao Jiang; Yong Wang; Run Zhou; Huiwu Liao (Desalination, 2026)

miR-23a modulates chlorantraniliprole susceptibility by targeting SfGSTs3 in Spodoptera frugiperda (Smith) - Fan-Bin Kong; Yong-Po Lv; Bai-Zhong Zhang; Meng-Yuan Zhang; Ling-Ling Cui; Ren-Jie Li; Dong-Mei Chen; Yu-Yang Peng; Run-Qiang Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Anion-modulated Cu8 nanoclusters as high-performance hypergolic fuels enabled by low-concentration oxidizer - Run-Meng Li; Chao Wang; Yan-Wen Chen; Guoqiang Sun; Xiao-Fei Liu; Shuang-Quan Zang (Chemical Engineering Journal, 2026)

Therapy-chemotherapy dual mode intelligent nano hydrogen generator for tumor treatment - Xuheng Chen; Hongxin Zhang; Yong Liu; Feiyu Zhao; Bowen Li; Run Yang; Niansong Qian; Yang Bai; Liang Zhao; Bin Zheng; Shanlong Zhang (Chemical Engineering Journal, 2026)

Dynamic oil fume exhaust method and calculation formula suitable for residential kitchens in cold regions - Kailiang Huang; Run Bai; Guohui Feng; Xiaoxu Li; Chaoying Fan; Helu Cao; Haipeng Yu (Building and Environment, 2026)

Analysis of odor and VOCs pollution in industrial parks of central inner Mongolia autonomous region based on mobile monitoring - Chaofei Li; Yuanhao Jia; Yu Qiu; Cheryl Marie Cordeiro; Sha Li; Yanying Chen; Jinxing Liu; Heinz W. Siesler; Hongkan Wu; Run Zhao (Atmospheric Environment, 2026)

A unified intracellular pH landscape with SITE-pHorin: a quantum-entanglement-enhanced pH probe - Shu-Ang Li; Xiao-Yan Meng; Su Zhang; Ying-Jie Zhang; Run-Zhou Yang; Dian-Dian Wang; Yang Yang; Pei-Pei Liu; Jian-Sheng Kang (Science China Life Sciences, 2026)

Cuproptosis Inhibition by C-Phycocyanin Confers Neuroprotection against Copper-Induced Mitochondrial Damage and Cognitive Impairment - Run Song; Junwan Fan; Jiannan Wu; Shiyi Yin; Ying Zhang; Shihe Jiang; Yan Li; Xin Zhao; Mengjiao Sun; Weina Jin; Wenyan He; Junqiang Yan (Molecular Neurobiology, 2026)

Cang-Ai Volatile Oil Mitigates Lipopolysaccharide-Induced Depressive-Like Behaviour in Mice by Modulating the Microglial BDNF/CREB Signaling Pathway - Lianna Zhao; Run Yin; Kailing Zhang; Jinqing Huang; Ruiyu Zheng; Youyang Zhu; Gang Li; Na Lei; Lei Xiong; Yuhuan Xie (Molecular Neurobiology, 2026)

Oral Administrations of Short-Chain Fatty Acids or Probiotics Extend the Survival Times and Mitigate the Neuropathological Damages in the Scrapie-Infected Hamsters - Yuan Wang; Dong-Lin Liang; Run-Dong Cao; Ruhan A.; Jia-Feng Zeng; Bing Xu; Ju-Zheng Li; Wei-Wei Zhang; Li-Ping Gao; Kang Xiao; Xiao-Ping Dong; Qi Shi (Molecular Neurobiology, 2026)

Cloning, heterologus expression and characterization of a thermophilic and salt tolerant GH11 xylanase from Allostreptomyces psammosilenae YIM DR4008T - Xin-Wei Li; Dan Zhu; Lei Li; Run-Feng Yang; Shi-Yuan Fan; Zhi-Hua Lv; Meng-Di Rao; Rong-Huang Song; Peng Sang; Yi-Rui Yin; Li-Quan Yang (Antonie van Leeuwenhoek, 2026)

Identification of lncRNAs Associated with Imidacloprid Resistance in the Grain Aphid Rhopalosiphum padi (L.) (Hemiptera: Aphididae) - Ling-Ling Cui; Yong-Po Lv; Ren-Jie Li; Yu-Tai Jiang; Bai-Zhong Zhang; Yu-Yang Peng; Jin-Song Zheng; Fan-Bin Kong; Run-Qiang Liu (Neotropical Entomology, 2025)

Target Fibroblast-B cell crosstalk via MIF signaling drives pathogenic B cell differentiation and joint damage in knee osteoarthritis - Bizhi Tu; Zheng Zhu; Yan Li; Zhengming Zhu; Shijie Wang; Peizhi Lu; Ya Li; Shuo Yang; Dingtao Hu; Run Fang; Rende Ning (Inflammation Research, 2025)

Insights into the combined effect of N2H4 and NH2OH on CANON process in SBR: Nitrogen removal performance, stability of process and microbial community - Zi-Yue Li; Run-Mei Li; Xin Ma; Jia-Min Zhou; Ying-Jun Sun; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Zi-Jun Yan; Qian-Qian Zhang; Zai-Yong Zhang (Journal of Environmental Chemical Engineering, 2025)

Facet-mediated degradation of 6PPD on hematite: From direct electron transfer to reactive oxygen species-driven accelerated oxidation - Chenghe Yan; Zekun Li; Run Xie; Qian Gu; Zhiyu Zhou; Mengning Xi; Yixuan Liu; Chi Zhang; Kecheng Zhu; Hanzhong Jia (Journal of Environmental Chemical Engineering, 2025)

Simultaneously regulating the content of pores and carbon microcrystallites in carbon blocks via coal tar pitch oxygen functionalization for improved mechanical and wear resisting performance - Yixing Chen; Sihan Gao; Pei Gong; Ping Liu; Jiao Tan; Xun He; Hong Luo; Run Li; Chuanjun Tu (Fuel, 2025)

Drinking water quality criteria value estimation for representative haloacetamide disinfection byproducts via a benchmark dose approach based on an association analysis between drinking water exposure and altered liver function in a community population in Wuxi from Jiangsu province - Shunan Wang; Jingying Zhu; Wanjun Zhang; Chao Yang; Lingling Xu; Limei Chen; Yao Li; Run Zhou; Xinliang Ding (Environmental Pollution, 2025)

Cluster-induced room-temperature phosphorescence of low-boiling-point non-conjugated organic small molecules - Li Gao; Wensheng Xu; Jiang Liu; Ligong Chen; Shengtian Wu; Run Wang; Ziyi Lu; Guoyi Bai; Bowei Wang (Chemical Engineering Journal, 2025)

A study on soil erodibility and the applicability of estimation methods in Robinia pseudoacacia L. mixed forests on the Loess Plateau, China - Jin-long Ma; Bing Wang; Run-hao Yu; Yan-fen Yang; Guo-bin Liu; Jing Wang; Cheng-fang Li (CATENA, 2025)

Transcriptomic profiling reveals mechanism, therapeutic potential, and prognostic value of cancer stemness characteristic in nasopharyngeal carcinoma - Jin-Wei Chen; Run-Nan Shen; Jiang-Quan Zhu; Ying-Hang Wang; Liang-Min Fu; Yu-Hang Chen; Jia-Zheng Cao; Jin-Huan Wei; Jun-Hang Luo; Jia-Ying Li; Cheng-Peng Gui (Functional & Integrative Genomics, 2025)

Elevated incubation temperature enhances the growth performance and increases the percentage of female offspring in the swimming crab, Portunus trituberculatus - Shurong Wu; Qingwei Chen; Ronghua Li; Run Tong; Chunlin Wang; Changkao Mu; Ce Shi; Weiwei Song (Aquaculture International, 2025)

Fast Forward Modeling of Resistivity Method under Complex Topography Using Finite Element Method - Zhan Wang; Chang-Wei Li; Yu-Zeng Lv; Run-Lin Luo; Bo Cheng; Bo Li (Applied Geophysics, 2025)

High-performance dynamic radiative regulation via controllable macroscopic materials modulation - Ya Huang; Xueke Wu; Siming Zhao; Baoshun Wang; Zhuojing Zhao; Di Gao; Run Li; Yunrui Li; Fei Wang; Fan Lan; Yanlong Zhao; Rufan Zhang (Science Bulletin, 2025)

Iridoids and other constituents from the aerial parts of Patrinia rupestris and their inhibitory effects on nitric oxide production - Zhi-Yuan Liu; Sheng-Run Guo; Jian-Xian Tang; Chun-Yan Zhao; Li Pu; Li-Zhong Wang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Phytochemistry, 2025)

Geological and geochemical characteristics of intermediate-basic intrusions in Funiushan area, southern margin of the North China Craton: Implications for tectonic environment and mantle properties in the Early Cretaceous - Wei Zeng; Feng-Yue Sun; Cheng-Dong Li; Zhi-Dan Li; Yin-Hang Cheng; Wen-Gang Liu; Jia-Run Tu; Chao Zhang; Xing Liu; Wei-Zhi Sun (Lithos, 2025)

Water quality analysis of organic pollutants in electronic industry manufacturing wastewater based on spectral analysis and molecular level exploration - Run Yuan; Yihe Qin; Han Li; Weiqing Huang; Haiming Huang; Xuwen He (Journal of Water Process Engineering, 2025)

The potential of anthraquinone-2-sulfonate (AQS) for “shell breaking” of iron-coated denitrification granular sludge - Xin-Rui Zhang; Zhi-Han Xi; Zi-Jun Yan; Xin-Tao Liu; Ying Wang; Run-Mei Li; Zi-Yue Li; Ke-Yu Wu; Ren-Cun Jin; Zai-Yong Zhang; Qian-Qian Zhang (Journal of Environmental Management, 2025)

A visualization-enhanced electrochemical sensing system with mobile data transmission for rapid 3-monochloropropane-1,2-diol detection - Ni Wu; Xiaojun Wang; Run Xu; Changxia Sun; Xinwei Li; Qiang Li (Food Chemistry, 2025)

Global synthesis of nitrogen management in sugarcane systems: Decoding climate-soil-management drivers of Brazil-China contrasts - Xiaomai Yuan; Shengsen Zhou; Fumin Wei; Li Ma; Yongfeng Sun; Dingjiao Peng; Run Liang; Yibao Luo; Baoshan Chen; Wei Yao; Ziting Wang (Field Crops Research, 2025)

Dual-gripper coordination effect stabilizing zinc anodes for high-performance zinc metal batteries - Tian-Yi Yang; Kun Li; Ting-Ting Su; Li Ma; Qiu-Shuai Xu; Chang-You Shao; Wen-Feng Ren; Run-Cang Sun (Chemical Engineering Journal, 2025)

Two-step fabrication of perovskite films with controlled crystal orientation via PbI₂ modulation for high-performance solar cells - Yixuan Wang; Shuheng Jiang; Mengjin Zhang; Zequn Ma; Huishu Li; Run Zhao; Hao Lu (Chemical Engineering Journal, 2025)

Environmental adaptive nanoplatform for bacteriotherapy - Wei Sun; Yang Bai; Xuefei Shao; Bowen Li; Haohua Yuan; Xuheng Chen; Run Yang; Yuan Liu; Shixiang Cheng; Yanguo Xi; Qing-hui Meng; Bin Zheng; et al. (Chemical Engineering Journal, 2025)

Waste biomass-derived organic matter for sustainable soil remediation: Enhancing heavy metal removal and eluent reuse in agricultural application - Shuai Yang; Chen Tu; Guo-ming Liu; Yuan Li; Yi Wang; Xia Zhu; Shao-cheng Si; Run-lai Luo; Zhong-yuan Li; Yong-ming Luo (Bioresource Technology, 2025)

Response of tomato growth and transpiration under adequate elevated CO2 concentrations coupled with irrigation regimes - Muhammad Akhlaq; Henglu Miao; Chuan Zhang; Run Xue; Haofang Yan; Muhammad Usman Hameed; Jun Li; Jiangtao Ren; Junaid Nawaz Chauhdary; Muhammad Mahmood Ur Rehman (Irrigation Science, 2025)

Microbial mineralization of struvite by using talc and its implications for phosphorus recovery - Xingtong Chen; Tianlei Zhao; Bing Li; Yihe Qin; Xiaoman Li; Run Yuan; Jingjing Chen; Han Li; Haiming Huang (Applied Clay Science, 2025)

Construction and optimization of a near-infrared spectroscopic model for the assessment of nitrogen and phosphorus in dairy farm slurry under different temperatures - Mengting Li; Shengbo Liu; Di Sun; Zengjun Yang; Run Zhao; Keqiang Zhang (Computers and Electronics in Agriculture, 2025)

A laser with instability reaching 4 × 10 - 17 based on a 10-cm-long silicon cavity at sub-5-K temperatures - Zhi-Ang Chen; Hao-Ran Zeng; Wen-Wei Wang; Han Zhang; Run-Qi Lei; Jian-Zhang Li; Cai-Yin Pang; She-Song Huang; Xibo Zhang (Science Bulletin, 2025)

Antibiotic resistance genes in multi-matrices of Chaohu Lake: Spatiotemporal variation and correlation with pesticides and PPCPs - Hao Yang; Hongwei Fu; Yutong Zhao; Run Li; Man Cao; Yi Liu; Yachao Ni; Wei Song; Yangyang Liang; Panyuan Cai; Wei Chang; Fangbiao Tao; et al. (Journal of Hazardous Materials, 2025)

Anion-exchange strategy boosts iodine adsorption in amorphous metal-organic cage-based extended networks - Tian-Tian Li; Pei Lai; Sheng-Run Zheng (Journal of Environmental Chemical Engineering, 2025)

The interactions, impacts, and removal strategies of microplastics (MPs) and antibiotic resistance genes (ARGs) in aquatic environments, particularly in wastewater treatment plants (WWTPs) - Ying Wang; Xin-Rui Zhang; Min-Min Qiang; Zheng Huang; Xin-Tao Liu; Run-Mei Li; Zi-Yue Li; Zai-Yong Zhang; Qian-Qian Zhang (Journal of Environmental Chemical Engineering, 2025)

Harnessing built-in electric fields for enhanced electron transfer in biosensor for precise digital health assessment - Tian-Run Lv; Yaqiong Yang; Jia-Chen Zhang; Ling Qi; Ming-Jie Yin; Yong Li; Ken Tye Yong; Quan-Fu An (Chemical Engineering Journal, 2025)

Design of organohydrogels with melt-adjustable mechanics via an “Oil-in-Water” biphasic network synergy for flexible strain sensor applications - Shao-Fei Sun; Wei He; Meng Li; Shaochao Sun; Changyou Shao; Ling-Ping Xiao; Run-Cang Sun (Chemical Engineering Journal, 2025)

Divergent effects of cropland management practices and global change factors on microbial necromass across ecosystems: implications for soil organic carbon - Chen-Hao Lyu; Wen-Jun He; Peng Chen; Xin-Xin Jing; Guo-Shi Zhang; Run-Qin Zhang; Zi-Yan Li; Zhi-Guo Li; Yi Liu (CATENA, 2025)

Factors contributing to high oxidative stability in oil from long-term stored tiger nut (Cyperus esculentus L.): Endogenous components - Jia-Ke Li; Deng-Ju Cai; Hang-Yu Zhao; Yu-Xiang Ma; Xiao-Shuang Cai; Hua-Min Liu; Run-Yang Zhang (Journal of Stored Products Research, 2025)

Decabromodiphenyl ethane induces intrauterine growth restriction by suppressing placental angiogenesis via TWIST2/NAT10-mediated ac4C-dependent TGF-β1 mRNA stabilization - Run Ling; Xin Yin; Liyao Ma; Yan Zhang; Yidan Ma; Rufei Gao; Yanqing Geng; Xinyi Mu; Xuemei Chen; Fangfang Li; Junlin He (Journal of Hazardous Materials, 2025)

Evolution mechanism of catalytic performance in piezo-photocatalytic recycled pervious concrete during hydration to carbonation - Hailiang Fei; Guanyu Liu; Jiayu Wu; Jiaxu Zhang; Yulong Zheng; Mingtao Run; Fen Li; Sanqiang Yang (Chemical Engineering Journal, 2025)

Post-dynamic behaviors of the saturated loess in the Zhongchuan slide triggered by the Jishishan M6.2 earthquake - Haiping Ma; Keliang Ren; Wenguo Ma; Youzhen Yang; Chen Li; Run Cai (Natural Hazards, 2025)

A strain of Rickettsia induces thelytoky in Anastatus gansuensis via maternal transmission - Run-Na Gong; Yong-Ming Chen; Jun-Bo Luan; Chen-Yi Li; Xiang Sun; Haneef Tariq; Lian-Sheng Zang (Journal of Pest Science, 2025)

The Impact of Tidal Effects on the Deformation and Internal Forces of Coastal Deep Excavations - Run-min Hao; Yan-kai Wu; Chang-hui Gao; Hui Li; Chun-ying Xia; Yuan-zhi Tan (Applied Geophysics, 2025)

Antithrombotic macrocyclic sesquiterpene pyridine alkaloids from Tripterygium hypoglaucum - Qiong Jin; Jia-Shan Shen; Xian-Run Wu; Hui-Zhen Peng; Zi-Hao Fu; Li-Qiang Chen; Yun-Li Zhao; Min Ye; Xiao-Dong Luo (Phytochemistry, 2025)

TSC2/mTORC1 integrates deoxynivalenol signals recognized by membrane receptors IR and EGFR to restrict intestinal stem cell function - Cai-xia Dou; Hao-zhan Qu; Ying-chao Qin; Xiao-fan Wang; Hui-chao Yan; Run-sheng Li; Yu-guang Zhao; Jia-yi Zhou; Xiu-qi Wang (Journal of Hazardous Materials, 2025)

Strong heterogeneity in laterally exchanged particulate organic matter across tidal marshes in a large river delta - Qi Wu; Hong-Sheng Cao; Youhei Yamashita; Christian Lønborg; Run Li; Jianzhong Ge; Hualei Yang; Bolin Liu; Jinzhou Du; Fang Cao (Environmental Research, 2025)

Piezo-photocatalytic NO degradation performance and load-light coupling mechanism of g-C3N4/BaTiO3 fog seal pavements - Guanyu Liu; Tianzheng Zhao; Jiayu Wu; Yaobin Zhan; Meicheng Kuang; Mingtao Run; Fen Li; Sanqiang Yang (Chemical Engineering Journal, 2025)

Laminaria Japonica hydrolysate as a novel biostimulant for enhancing DHA accumulation in Aurantiochytrium limacinum - Jia-Xue Lin; Ying Wang; Shao-Geng Zhao; Bei-Chen Huang; Yue Zhang; Zhi-Qiang Wang; Sheng-Jie Li; Qian Liu; Yan Ma; Jing-Run Ye; Hai-Ying Wang; Zhi-Peng Wang (World Journal of Microbiology and Biotechnology, 2025)

Target analysis of per- and polyfluoroalkyl substances in surface water: Occurrence, seasonal trends, and risk-based prioritization in the Minjiang River - Hui Zhang; Xin-Yue Wang; Yu-Hua Zheng; Jing-Run Hu; Xiao-Lin Li; Hong-Ling Yin; Rui Xiao; Xiao-Lan Zhu; Ting Chen; Huan Chen (Science of The Total Environment, 2025)

Formation and sensory properties of novel Pyrazinones in the Glycylalanine and Alanylglycine dipeptide Maillard reaction systems - Yue Luo; Run Li; Siyue Zhu; Qingrong Huang; Baojun Xu; Chi-Tang Ho (Food Chemistry, 2025)

Seasonally frozen soil characteristics and feasibility study of turf slope protection - Run Liu; Xiangning Du; Xiangchuan Meng; Chengfeng Li; Xiaolei Wang; Huan Zhang; Chun Liu (Bulletin of Engineering Geology and the Environment, 2025)

Resilience Assessment of Tomato Crop Chlorophyll Fluorescence Against Water Stress Under Elevated CO 2 and Protective Cultivation - Muhammad Akhlaq; Henglu Miao; Chuan Zhang; Haofang Yan; Xue Run; Junaid Nawaz Chauhdary; Muhammad Mahmood ur Rehman; Jun Li; Jiangtao Ren (Irrigation and Drainage, 2025)
Water scarcity is a crucial issue that reduces plant growth and yield worldwide. Chlorophyll fluorescence parameters, which are associated with plant growth and yield under water stress, are the most sensitive plant parameters. The mitigation of water stress by elevated CO 2 (e[CO 2 ]) by chlorophyll fluorescence for tomato growth is rare. Tomato plants were grown in a controlled environment chambers (CECs) under eight treatments under controlled environmental conditions for two growing seasons: autumn–winter ( AW ) 2021 and spring–summer ( SS ) 2022. The four irrigation regimes included 40%–50% soil water holding capacity (WHC) (I 1 ), 60%–70% WHC (I 2 ), 80%–90% WHC (I 3 ) and 100% WHC (I 4 ). Eight treatments of four irrigation regimes coupled with e[CO 2 ] (700 μmol·mol −1 ) and ambient CO 2 (a[CO 2 ], 500 μmol·mol −1 ) were designed, respectively: I 1 e[CO 2 ], I 2 e[CO 2 ], I 3 e[CO 2 ], I 4 e[CO 2 ], I 1 a[CO 2 ], I 2 a[CO 2 ], I 3 a[CO 2 ] and I 4 a[CO 2 ], where I 4 a[CO 2 ] was considered the control treatment (CK). The chlorophyll fluorescence parameters maximum photochemical efficiency of PSII ( F v /F m ), photochemical efficiency of PSII ( Ф PSII ), electron transport rate ( ETR ) and photochemical quenching ( qP ) significantly decreased, whereas nonphotochemical quenching ( NPQ ) significantly increased under drought stress. Compared with that under CK, the maximum reduction in F v /F m under I 1 a[CO 2 ] was 14% in AW 2021, whereas it was 19% in SS 2022. The Ф PSII was reduced by 13%–3% and 13%–6% under I 1 a[CO 2 ] in AW 2021 and SS 2022, respectively (under the fixed photosynthetically active radiation range of 125–625 μmol·m −2 ·s −1 ) compared with that in the CK. The ETR and qP decreased under I 1 a[CO 2 ] at their maximum level in AW 2021 and SS 2022 with respect to those in the CK. The results showed that e[CO 2 ] mitigated water stress as the F v /F m , Ф PSII , ETR and qP were increased under water stress coupled with e[CO 2 ]. I 1 e[CO 2 ] was the most influential treatment for chlorophyll fluorescence parameters assessed via principal component analysis ( PCA ) in AW 2021 and SS 2022. This study explained the approach to develop crop resilience against water stress by inducing e[CO 2 ], which will play a vital role in sustainable agriculture under drought stress.

A Study of the Global Buckling Response and Control Measures for Snake-Laid Pipelines Under Uneven Soil Resistances - Runnan Miao; Xiang Sun; Chengfeng Li; Run Liu; Xiangning Du; Yinuo Liu (Journal of Marine Science and Engineering, 2025)
The snake-laying method is widely employed as an effective strategy for global buckling mitigation in submarine pipelines. The uneven distribution of soil resistance along pipeline routes significantly amplifies the complexity of global buckling responses in snake-laid pipelines and challenges their control mechanisms. This study establishes a finite element computational model to investigate the effects of soil resistance distribution gradients and patterns along pipeline routes, alongside their coupling with critical snake-laying parameters (spacing, offset, curvature). The research revealed that an uneven distribution of soil resistance can induce the global buckling submersion phenomenon in snake-laid pipelines. Among the critical snake-laying parameters, curvature enhancement proves to be the most effective mitigation strategy against the global buckling submersion phenomenon. Additionally, an improvement in the conventional uniform-laying scheme is proposed for uneven soil resistance distribution: the originally planned snake-laid section can be replaced by a straight pipeline section in the high-resistance zone. This study provides enhanced technical solutions for global buckling prevention in pipelines traversing uneven seabeds.

Characterizing Post-Storm Beach Recovery Modes: A Field-Based Morphodynamic Study from Dongdao Beach, China - Lulu Liu; Yan Sun; Run Liu; Daoheng Zhu; Zhaoguang Chen; Zhiqiang Li (Journal of Marine Science and Engineering, 2025)
The post-storm beach recovery process exhibits variability. Understanding its mechanisms is crucial for advancing the study of beach morphodynamics. This study involved a 25-day continuous field observation on Dongdao Beach, Hailing Island, Yangjiang City, Guangdong Province, following the passage of Typhoon Cempaka. The evolution of beach morphology and the spatiotemporal variations in erosion and accretion were analyzed to explore the key influencing factors, response mechanisms, and recovery modes during the short-term recovery process. The post-storm evolution of beach profile structures is predominantly influenced by major geomorphic units such as berms and sandbars, whereas localized responses are characterized by adjustments of fine-scale features like micro-troughs. The width of the supratidal zone and the position of the berm crest continuously fluctuate, while the slope of the intertidal zone increases or decreases as the berm crest migrates landward or seaward. The erosion–accretion process was complex and occurred in distinct stages, with marked spatial heterogeneity. In some areas, the beach experienced multiple short-term cycles of alternating erosion and accretion. Beach slope plays a significant role in short-term recovery. Three types of response relationships between beach unit-width volume and changes in slope were observed, with flatter beaches being more sensitive to changes in unit-width volume. Based on this, four recovery modes in the post-storm short-term recovery process were explored from the perspective of beach slope. This study provides theoretical support for managing beaches after storms and recommends the implementation of zoned and phased management strategies based on different recovery modes to enhance the efficiency and resilience of coastal recovery.

Study on the lateral breakout resistance of submarine pipelines in the sand wave area - Run Liu; Yinze Guan; Chengfeng Li; Xiang Sun; Yinuo Liu; Zheng Yu (Ocean Engineering, 2025)

Elucidating the influence of alumina mineral on sodium storage performance of biomass-derived hard carbon anode - Hang Guo; Jia-He Lv; Run-Dong He; Bin He; Xiao-Ling Dong; Wen-Cui Li (Fuel, 2025)

The association between greenspace exposure and sperm quality: A retrospective cohort study focusing on sperm kinematics and the influence of buffer settings - Sixuan Zeng; Tingting Yang; Run Tian; Xin Jin; Lu Zhang; Fuping Li; Leyao Fu; Jiarui Cai; Junhao Liao; Guishuang Song; Xiaoli Luo; Yujue Wang; et al. (Environmental Research, 2025)

Multi-active-site antibacterial modification of dopamine-hyaluronic acid hydrogel with N-halamine for skin tissue engineering - Chenghao Li; Saren Gerile; Nan Du; Liang Zou; Zhiqiang Wang; Yanfang Liu; Jili Hou; Kuntong Song; Yuanhao Xiao; Hui Ren; Jing Kang; Alideertu Dong; et al. (Carbohydrate Polymers, 2025)

Arbuscular mycorrhizal fungi enhance Leymus chinensis resistance to salinity predominantly through regulating root endosphere bacteria - Peiran Guo; Yazhou Hou; Bingbing Jia; Yuchen Wang; Chengyan Lu; Run Wang; Jiaying Lin; Yanan Zhang; Wei Guo; Frank Yonghong Li (Plant and Soil, 2025)

Positive Dose–Response Relationship Between Urinary Trihalomethanes and Blood Pressure in Adults in Wuxi, China - Shunan Wang; Qianqian Wang; Chao Yang; Li Yang; Lingling Xu; Run Zhou; Limei Chen; Yao Li; Pengfei Zhu; Xinliang Ding (Exposure and Health, 2025)

Physiological, transcriptomic and metabolomic responses of the marine diatom Phaeodactylum tricornutum to the auxin IAA - Yu-Ting Chen; Dong-Sheng Zhao; Xiao-Li Liu; Huan Yang; Run-Ze Gu; Nan Li; Xiufeng Yan; Hui-Xi Zou (Algal Research, 2025)

Low-temperature catalytic oxidation of toluene using CeO2@MIL-101(Fe): Stability against water and SO2 - David Murindababisha; Abubakar Yusuf; Kien-Woh Kow; Yong Sun; Run Pan; Yong Ren; George Zheng Chen; Jianrong Li; Chengjun Wang; Jun He (Process Safety and Environmental Protection, 2025)

Dating fluvial terraces on the southeastern Tibetan Plateau using the uranium comminution age method - Run Zhang; Laifeng Li; Xianyan Wang; David William Hedding; Jinyu Zhang; Le Li; Zhewen Xu; Shenghui Ouyang; Gaojun Li (Quaternary Science Reviews, 2025)

Enhancing fruit quality through unraveling the molecular and physiological basis and preventing cracking in jujube (Ziziphus jujuba Mill.) - Hong-Xiang Zhou; Run-Zhe Wang; Wen-Ting Luo; Yang Liang; Shi-Yu Liu; Juan Chen; Ji-Qing Peng; Yan-Xia Fan; Shu-Zhan Li; Chuan Guo; Zi-Qiang Zhang; Feng-Xia Shao; et al. (Postharvest Biology and Technology, 2025)

Unveiling active nitrate and nitrite cycling in a eutrophic coastal bay, southern China from a dual isotope perspective - Zixuan Li; Hantao Zhou; Minfang Zheng; Mengya Chen; Run Zhang; Min Chen (Marine Environmental Research, 2025)

Insight into the influence of slight air oxidation on the carbonization behavior of pitch/calcined coke mixture to deliver high-performance graphite blocks - Pei Gong; Chongwei Li; Jiao Tan; Ping Liu; Xun He; Yixing Chen; Xiaobin Zeng; Run Li; Chuanjun Tu (Fuel, 2025)

Enhanced activation of peroxymonosulfate by nickel sulfide with sulfur vacancies for ultrafast organic pollutants degradation: Roles of active sites and mechanism - Cai-Wu Luo; Liang Jiang; Xian-Feng Li; Qiang-Mao Wan; Tian-Jiao Jiang; Sen-Ping Mao; Jing-Qian Guo; Run-Ze Zhao; Chao Xie (Environmental Pollution, 2025)

Reexamination and reidentification of ocean oxygenation event in the wake of the Marinoan glaciation - Run Li; Xiqiang Zhou; Chuan Guo; Taiyu Huang; Zhenfei Wang; Kang-Jun Huang; Peng Peng; Xiangli Wang; Tongxuan Du; Dingshuai Xue; Yanhong Liu (Earth and Planetary Science Letters, 2025)

Mechanochemical treatment boosted microwave-assisted sulfonation of softwood lignin for the fabrication of dye dispersant - Xu Fu; Ling-Ping Xiao; Bo-Wen Meng; Wen-Jie Li; Run-Cang Sun (Chemical Engineering Journal, 2025)

Methyl jasmonate induces the regulation of protostane triterpene biosynthesis by microRNAs in Alisma orientale - Wenyuan Run; Tao Li; Shengyuan Wang; Shan Xiao; YuHeng Wu; Wei Gu (Protoplasma, 2025)

Ecoenzymatic stoichiometry reveals the exacerbation of microbial C and N limitations by moss crusts in degraded karst ecosystems - Minghao Deng; Jiaojiao Wu; Xin Zhao; Dong Chen; Guanting Guo; Mingzhong Long; Qimei Wu; Run Liu; Xiaona Li (Applied Soil Ecology, 2025)

An azacrown ether-based near-infrared fluorescent probe for the detection of Pb2+ and its applications in food, environmental water, plant and animal samples - Yueyuan Zhang; Huacong Wei; Yu Li; Zhuye Shang; Run Zhang; Zhiqiang Zhang; Qingtao Meng (Analytica Chimica Acta, 2025)

Three new maaliane-type sesquiterpenoids from the roots and rhizomes of Valeriana officinalis var. latifolia - Jia-Jin Liu; Sheng-Run Guo; Hou Zhu; Dan Liu; Hong-Mei Li; Rong-Tao Li (Phytochemistry Letters, 2025)

Highly efficient and convenient QuEChERS using ZIF-67 derived magnetic nanoporous carbon for determination of carbamate pesticides in various vegetable and fruit samples - Zi-Ling Li; Xiao-Run Qi; Yi-Heng Xu; Jia-Qi Zhao; Gui-Fu Zuo; Man-Man Wang (Food Chemistry, 2025)

Study on methane flux variation characteristics and regulation mechanisms in urban wetlands under different restoration years and moisture gradients - Qing Liu; Chun Feng; Run Li; Yun Zhou; Xin Meng; Hua Liu (Environmental Research, 2025)

Co species modulating of BiOBr-based Z-scheme heterojunction for the transform photoreduction CO2 products from CO to CH4 - Run-Jing You; Kuan Wang; Huan Ma; Xin-Peng Li; Zhe Cao; Zhen-Hong He; Huan Wang; Weitao Wang; Xiaojuan Lai; Zhao-Tie Liu (Chemical Engineering Journal, 2025)

Effects of alternating wet and dry irrigation regimes on rice growth and physiology characteristics in southeast China - Rui Zhou; Haofang Yan; Chuan Zhang; Xingye Zhu; Guoqing Wang; Bin He; Kinda Negessa Disasa; Imran Ali Lakhiar; Run Xue; Yudong Zhou; Biyu Wang; Jun Li; et al. (Paddy and Water Environment, 2025)

Exploring the multifaceted roles of histone deacetylase inhibitor vorinostat in the cell growth, mycelial morphology, pigments, and citrinin biosynthesis of Monascus purpureus - Run-Ya Li; Chen-Yu Zhang; Shaoxiang Xiao; Xin-Yi Liu; Ru-Xue Li; Jing Li; Hao Li; Jun Liu (Archives of Microbiology, 2025)

Endophytes and soil microorganisms participate in the germination of Sinojackia xylocarpa Hu by degrading the pericarp - Zi-Hao Li; Xin-Yi Ma; Huan Yang; Run-Guo Zang; Jia-Ru Li (Acta Physiologiae Plantarum, 2025)

Evolution law and calculation model of closure time in artificial ground freezing - Xu Li; Shuang Liu; Xiao-kang Li; Zu-run Yue (Tunnelling and Underground Space Technology, 2025)

A modified h-form hydrothermal coupling simulation method for frozen soil - Run-ze Tian; Xu Li; Xiao-kang Li; Zhi-yuan Zhang; Shuang-jie Wang; Qian Wang (Computers and Geotechnics, 2025)

Understanding the impact of promoters on enhancing and inhibiting the sulphur resistance and regeneration of supported Pd catalysts for complete methane oxidation - Abubakar Yusuf; Yong Ren; Yun Liu; Li Shi; Zhiyu Xiao; Run Pan; Zheng Wang; Hainam Do; Jianrong Li; Jun He (Chemical Engineering Journal, 2025)

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

Boosting structural stability and air stability towards layered oxide cathodes for potassium ion batteries - Hong Chen; Lu-Kang Zhao; Xuejiao Cheng; Xuan-Wen Gao; Zhaomeng Liu; She-Dong Li; Dong-Run Yang; Tian-Zhen Ren; Wen-Bin Luo (Chemical Engineering Journal, 2025)

Study on the feasibility of buckwheat as a trap plant for flower thrips (Frankliniella intonsa) in sunflower field - Hui Qu; Jing Chang; Ze-Run Chuai; Wen-Bing Zhang; Jian Zhang; Jun Zhao; Hai-Ping Li (Journal of Pest Science, 2025)

Creep constitutive model of yellow sandstone under coupling action of unloading and wet-dry cyclic damage - Zhe Qin; Zhen Liu; Run-chang Zhang; Hou-li Fu (Journal of Mountain Science, 2025)

Centrifuge model study of vertical ultimate bearing capacity of pile foundations in overconsolidated clay - Run Liu; Yu Jiang; Chengfeng Li; Guangsi Chen; Chunyang Su; Xiaoyu Long (Ocean Engineering, 2025)

Bearing capacity profile for laterally loaded piles in clay - Tianliang Li; Chao Liang; Run Liu (Ocean Engineering, 2025)

Methane production related to microbiota in dairy cattle feces - Jian Liu; Meng Zhou; Lifeng Zhou; Run Dang; Leilei Xiao; Yang Tan; Meng Li; Jiafeng Yu; Peng Zhang; Marcela Hernández; Eric Lichtfouse (Environmental Research, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

An improved algorithm for salient object detection of microscope based on U2-Net - Yunchai Li; Run Fang; Nangang Zhang; Chengsheng Liao; Xiaochang Chen; Xiaoyu Wang; Yunfei Luo; Leheng Li; Min Mao; Yunlong Zhang (Medical & Biological Engineering & Computing, 2025)

From metabolomics to therapeutics: identifying causal metabolites and potential drugs for the treatment of osteoarthritis - Heng Li; Jingyan Sun; Jiewen Zhang; Yang Chen; Yiwei Zhao; Ruomu Cao; Ning Kong; Xudong Duan; Huanshuai Guan; Run Tian; Kunzheng Wang; Pei Yang (Inflammopharmacology, 2025)

Planar Hall plateau in magnetic Weyl semimetals - Lei Li; Chaoxi Cui; Run-Wu Zhang; Zhi-Ming Yu; Yugui Yao (Science Bulletin, 2025)

Effect of ignition timing on combustion characteristics and emissions of an X-type rotary engine with the high efficiency hybrid cycle - Run Zou; Feng Li; Jinxiang Liu; Wei Yang; Lijun Lei; Lei Zhang (Fuel, 2025)

The link between eye movements and cognitive function in mild to moderate Alzheimer’s disease - Xiao-ting Ma; Lin-lin Yao; Shan-wen Liu; Xiao-fen Weng; Run-ying Bao; Yi-fan Yang; Yi-feng Li; Yan-yun Sun; Dan Xu; Zhen-yu Jia; Hua Hu (Experimental Brain Research, 2025)

A domain-decomposition-based parallel approach for 3D geological modeling using radial basis functions interpolation on GPUs - Hong Li; Huizhu Ni; Jinming Fu; Bo Wan; Deping Chu; Fang Fang; Run Wang; Guoxi Ma; Xin Zhou (Earth Science Informatics, 2025)

Tri-functional molecular junction photocatalyst for cascade synthesis of N-benzylideneaniline derivatives - Xiao-Xin Li; Xiao-Xuan Hong; Zi-Yi Liao; Lei Zhang; Run-Han Li; Ying Zeng; Yue Liu; Shun-Li Li; Ya-Qian Lan (Science Bulletin, 2024)

Kopsileuconines A−D: Bisindole alkaloids with cytotoxic activity from Kopsia hainanensis - Ni-Ping Li; Shan-Na Chen; Wei-Fang Su; Fen Liu; Lian-Jing Li; Jian-Guo Song; Min-Jing Cheng; Yi-Yi Li; Run-Qiang Chen; Xue-Ping Lei; Wen-Cai Ye; Lei Wang (Phytochemistry, 2024)

Padeye positioning of composite bucket foundation for joint exploitation of offshore wind turbines and floating photovoltaics - Qingxin Li; Chengfeng Li; Run Liu (Ocean Engineering, 2024)

Synchrotron-based P K-edge XANES spectroscopy reveals the transition of phosphorus cycling in the early Cambrian ocean - Pengcheng Ju; Zhenfei Wang; Chao Chang; Zhangqin Zheng; Run Li; Wenpeng Xia; Xuyang Cao; Yigui Han; Mingyu Zhao; Chao Li; Xingliang Zhang; Kang-Jun Huang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Homogeneous tokenizer matters: Homogeneous visual tokenizer for remote sensing image understanding - Run Shao; Zhaoyang Zhang; Chao Tao; Yunsheng Zhang; Chengli Peng; Haifeng Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Promoting role of nitrogen-fixing bacteria and biochar on nitrogen retention and degradation of PBAT plastics during composting - Linshan Wang; Yanjiao Qi; Long Cao; Lisha Song; Run Hu; Qian Li; Yamin Zhao; Junyan Liu; Hong Zhang (Environmental Pollution, 2024)

Assessment of multidimensional diversity and conservation of threatened timber trees in China under climate change - Jian-Lin Hu; Xiu-Qin Ci; Xiao-Yan Zhang; Run Zhou; Jian-Hua Xiao; Zhi-Fang Liu; Can-Yu Zhang; Xuan Jin; Jie Li (Biological Conservation, 2024)

Overexpression of wheat C2H2 zinc finger protein transcription factor TaZAT8-5B enhances drought tolerance and root growth in Arabidopsis thaliana - Lulu Chen; Run Wang; Xiaoqing Hu; Dan Wang; Yuexia Wang; Ruili Xue; Mingzhu Wu; Hua Li (Planta, 2024)

Investigation on a Regulatory Framework for Seed Transportation of Spartina alterniflora in the Presence of Tidal Currents: A Case Study of Zhanhua District, Binzhou, China - Sheng Li; Shaomin Jing; Wanjun Jiang; Huanyu Zhang; Ye Yao; Mingju Gong; Run Liu (Journal of Ocean University of China, 2024)

Undrained Capacity of a Bucket Foundation with a Limited-Tension Interface for Offshore Wind Turbines - Jiayu Wang; Bin Li; Run Liu; Xu Yang; Chao Liang (Journal of Ocean University of China, 2024)

Study on the thermo-hydraulic behaviors within a CiADS 61-pin wire-wrapped fuel assembly under porous blockage conditions based on LBEblockageFoam - Yun-Xiang Li; Run-Sheng Yang; Yue Li; Xing-Kang Su; Yi-Wen Han; Zi-Nan Huang; Lu Meng; Song Li; You-Peng Zhang; Lu Zhang; Wei Jiang (Annals of Nuclear Energy, 2024)

Resistivity tomography based on multichannel electrodes - Fu-yu Jiang; Jiong Ni; Hai-jun Chen; Li-kun Gao; Song Chen; Xian-wei Wu; Zhi-qiang Su; Yao Lei; Ming-hui Dai; Run Han; Jun-kai Yu (Applied Geophysics, 2024)

Cadmium and pyrene in the soil modify the properties of earthworm-mediated soil - Zhiming Shi; Jie Yan; Run Su; Shuyu Shi; Wenwen Li; Yonghua Zhao; Juan Zhang; Congying Wang (Science of The Total Environment, 2024)

A new framework for assessing and dealing with heat risk from an urban resilience perspective - Teng Zhang; Yixuan Sun; Run Wang; Yong Yang; Le Yin; Liangang Li; Baolei Zhang (Journal of Cleaner Production, 2024)

The potential of glycinin basic peptide derived from soybean as a promising candidate for the natural food additive and preservative: A review - Hou-Qi Ning; Hai-Run Fan; Chun-Ling Yang; Gui-Jin Sun; Ying-Qiu Li; Hai-Zhen Mo (Food Chemistry, 2024)

MGDA-assisted plant washing agent for improving the removal of Cd and Cu from farmland soils - Yi Wang; Chen Tu; Yuan Li; Shuai Yang; Ying Liu; Xia Zhu; Shao-cheng Si; Run-lai Luo; Xiang-liang Pan; Yong-ming Luo (Environmental Pollution, 2024)

Laminar burning characteristics of ammonia and hydrogen blends at elevated initial pressures up to 2.5 MPa - Ning Wang; Tie Li; Xinpeng Guo; Zehao Wu; Shuai Huang; Xinyi Zhou; Shiyan Li; Run Chen (Chemical Engineering Journal, 2024)

Circ-Bptf Ameliorates Learning and Memory Impairments via the miR-138-5p/p62 Axis in APP/PS1 Mice - Hong-Fang Wang; Yi-Bo Li; Zi-Yu Liu; Wen-Meng Xie; Qing Liu; Run-Jiao Zhang; Wen-Yu Wang; Jia-Xin Hao; Lei Wang; Dan-Dan Geng (Molecular Neurobiology, 2024)

Exercise Alleviates Fluoride-Induced Learning and Memory Impairment in Mice: Role of miR-206-3p and PREG - Lei Chai; Qiqi Cao; Ke Liu; Run Zhu; Hao Li; Yanghuan Yu; Jixiang Wang; Ruiyan Niu; Ding Zhang; Bo Yang; Mohammad Mehdi Ommati; Zilong Sun (Biological Trace Element Research, 2024)

Evaluation of the applicability of beach erosion and accretion index in Qiongzhou Strait of China - Lulu Liu; Yan Sun; Run Liu; Xiaobo Wei; Zhiqiang Li (Frontiers in Marine Science, 2024)
In coastal erosion studies, the erosion and accretion index is a vital research tool for analyzing types of erosion and accretion. This index is primarily empirical or semi-empirical and is usually validated through tank experiments or open beach datasets, resulting in significant variation across different beach environments. In this study, 11 beach profiles of eight beaches measured along the Qiongzhou Strait in China, measured from 2018 to 2021, were analyzed to quantitatively determine coastal erosion or accretion by calculating each profile’s volume change per unit width. Additionally, sediment and wave data were used to calculate five erosion and accretion indices monthly to determine erosion and accretion conditions. These conditions were then compared with actual beach erosion and accretion data to evaluate the applicability of various discriminant indices. Furthermore, optimizing the threshold values of discriminant indices. The results show that: (1) Overall annual erosion and accretion are minimal, but seasonal variation is significant for beaches on both sides of the Qiongzhou Strait; (2) The five discriminant indices have some limitations in this study area, necessitating careful consideration when applying them to headland bay arc-shaped beaches with fetch-limited environments like the Qiongzhou Strait; (3) The selection of discriminant index parameters and their respective contribution degree of each parameter affects the formula’s applicability, with two-parameter formulas proving superior to the three-parameter formula in the study area; (4) Beach environmental factors, particularly those influenced by headlands and fetch-limited environments, impact the indices’ applicability; (5) Increasing the threshold value to a certain extent can improve the formula’s applicability.

Carbon–sulfur–calcium isotopic variability of lower Cambrian shale-hosted carbonate concretions: Insights into growth mechanisms and calcium cycling - Xiqiang Zhou; Xiyuan Chen; Tongxuan Du; Jian Sun; Dongjie Tang; Run Li; Kang-Jun Huang; Yi Ding; Daizhao Chen (Sedimentary Geology, 2024)

A dynamic evolutionary game to discourage enterprise “greenwashing” - Jian Xue; Run Li; Yan Li; Laijun Zhao (Journal of Cleaner Production, 2024)

Suppressed testicular macrophage M1 polarization by HDAC5 enforces insensitivity to LPS-elicited blood-testis barrier damage - Hao Li; Yi-Fan Hu; Xin-Run Wang; Kong-Wen Ouyang; Hua Wang; Kai-Wen Wang; Wei Chang; Jin Zhang; Zhi Yuan; Yong-Wei Xiong; Hua-Long Zhu; Lan Yang; et al. (Food and Chemical Toxicology, 2024)

Dual-Functional group passivation to foster buried interface Cohesion for High-Performance perovskite photovoltaics - Namatullah Nizamani; Kai-Li Wang; Run-Jun Jin; Chun-Hao Chen; Jing Chen; Yu Xia; Lei Huang; Yu-Han Li; Mary Donnabelle Balela; Zhao-Kui Wang; Liang-Sheng Liao (Chemical Engineering Journal, 2024)

Aerobic granular sludge for swine wastewater treatment: Implications for antibiotic and antibiotic resistance gene elimination - Meng-Yuan Li; Run-Dong Zhang; Shuang-Shuang Liu; Cheng-Lei Pei; Liang-Ying He; Jian-Liang Zhao; You-Sheng Liu; Yi-Jing Shi; Guang-Guo Ying (Bioresource Technology, 2024)

Validation and revision of low latitudes cloud base height from ERA5 - Dan Li; Yuzhi Liu; Run Luo; Weiqi Tang; Jie Gao; Ziyuan Tan (Atmospheric Research, 2024)

Development and Application of a Mitochondrial Genetically Encoded Voltage Indicator in Narcosis - Run-Zhou Yang; Dian-Dian Wang; Sen-Miao Li; Pei-Pei Liu; Jian-Sheng Kang (Neuroscience Bulletin, 2024)

Experimental Study on Multistage Seismic Damage Process of Bedding Rock Slope: A Case Study of the Xinmo Landslide - Jing-Jing Tian; Tian-Tao Li; Xiang-Jun Pei; Jian Guo; Shou-Dao Wang; Hao Sun; Pei-Zhang Yang; Run-Qiu Huang (Journal of Earth Science, 2024)

Novel separate aeration self-circulating technology for continuous aerobic granular sludge process: Performance evaluation, hydrodynamic simulation and control strategy - Wei-Kang Qi; Run-Feng Tian; Bo Li; Shu-Jun Zhang; Yong-Zhen Peng; Cong Wang (Water Research, 2024)

Relationship between human activities and environmental changes in the southern Tibetan Plateau since the Little Ice Age - Cunlin Li; Liping Zhu; Qingfeng Ma; Jianting Ju; Jiuju Cheng; Marco A. Aquino-López; Run Zhang; Qiangqiang Kou; Xinmiao Lü; Junbo Wang (Science of The Total Environment, 2024)

Structurally diverse diterpenoids from the seeds of Caesalpinia minax Hance and their bioactivities - Wen-Chao Tu; Lin-Fen Ding; Liu-Dong Song; Yong-Jiao Li; Run-Cheng Yan; Yun Wu; Wei-Yang Feng; Xing-De Wu (Phytochemistry, 2024)

Vibration reduction and efficiency enhancement effects of twisted rudders in submarines under small rudder angle conditions - Di Zhang; Jin-ming Ye; Wan-li Yang; Yuan-run Wu; Jian-lin Shou (Ocean Engineering, 2024)

Ecotoxicological assessment, oxidative response, and enzyme activity disorder of the rotifer Brachionus asplanchnoidis exposed to a toxic cocktail of spent lithium-ion battery leachate - Yi-fan Feng; Yu Zhang; Run-jia Yang; Si-qi Li; Xiao-jie Liu; Cui Han; Yi-fu Xing; Jia-xin Yang (Journal of Hazardous Materials, 2024)

Corrigendum to “Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots” [Chem. Eng. J. 486 (2024) 150196] - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Effect of metal cation crosslinking on the mechanical properties and shrimp freshness monitoring sensitivity of pectin/carboxymethyl cellulose sodium/anthocyanin intelligent films - Run Ji; Xinhua Zhang; Zhao Chen; Shuang Song; Yingying Li; Xiuling Zhang; Wentao Zhang (Carbohydrate Polymers, 2024)

Genome-wide analysis of long non-coding RNAs involved in the fruit development process of Cucumis melo Baogua - Ya-hui Li; Chun Liu; Run-zhe Xu; Yu-peng Fan; Ji-yuan Wang; Hu Li; Jian Zhang; Hui-jun Zhang; Jing-jing Wang; Da-kui Li (Physiology and Molecular Biology of Plants, 2024)

Roles of tropical-Pacific interannual–interdecadal variability in forming the super long La Niña events - Run Wang; Hong-Li Ren; Minghong Liu (Climate Dynamics, 2024)

Plasma Deoxycholic Acid Levels are Associated with Hemodynamic and Clinical Outcomes in Acute Pulmonary Embolism Patients - Na Sun; Yi-Qiang Chen; Yan-Sheng Chen; Lei Gao; Run-Wei Deng; Jing Huang; You-Li Fan; Xuan Gao; Bin-Feng Sun; Na-Na Dong; Bo Yu; Xia Gu; et al. (Cardiovascular Toxicology, 2024)

A temporal gap filling approach for GNSS-IR soil moisture inversion based on generalized extension - Haodong Zhao; Junna Shang; Fangzhou Li; Huli Shi; Run Pang (Advances in Space Research, 2024)

Study on the motion patterns of shallow-embedded pipelines in sand - Run Liu; Zheng Yu; Chengfeng Li; Xintong Hao (Marine Georesources & Geotechnology, 2024)

Mitigation of ammonia and hydrogen sulfide emissions during aerobic composting of laying hen waste through NaOH-modified biochar - Ze Cao; Run Zhu; Yong Li; Apurva Kakade; Shiyu Zhang; Yilin Yuan; Yinbao Wu; Jiandui Mi (Journal of Environmental Management, 2024)

Numerical modelling of sand liquefaction via a weakly coupled approach between lattice spring and discrete element methods - Zhe Li; Gao-Feng Zhao; Yu-Jie Zhang; Zhi-Peng Hao; Kai-Li Niu; Run Liu (Computers and Geotechnics, 2024)

Immobilization of Nickel- and Cobalt-Based Complexes in NH2-UiO-66 for Efficient CO2 Photoreduction - Yu Jiang; Si-Chao Liu; Li-Ping Zhang; Guo-Wei Guan; Yi-Tao Li; Shuang Ni; Run-Yuan Jiang; Su-Tao Zheng; Hao-Ran Liu; Hao-Ling Lan; Qing-Yuan Yang (Chemical Engineering Journal, 2024)

Liquid metal micrometer fibers with chain-bead structure for precision sewing in smart textiles applications - Feng Xu; Huiyun Xiao; Yuanzhao Wu; Fali Li; Haifeng Zhang; Jinyun Liu; Zidong He; Shiying Li; Qi Zhang; Xingjian Lu; Jie Shang; Yiwei Liu; et al. (Chemical Engineering Journal, 2024)

Strong concentration gradient effect and weak solvation effect in thermopower enhancement in K3Fe(CN)6/ K4Fe(CN)6 aqueous electrolyte with ethanol addition - Shouze Li; Zhou Li; Dongyan Xu; Run Hu (Chemical Engineering Journal, 2024)

Occurrence and mechanism of sulfamethoxazole in alginate-like extracellular polymers from excess sludge - Chen Shi; Ming Cheng; Run-Gen Zeng; Cong-Cong Li; Qian Wang; Li-Ting Hao; Ran-Bin Liu; Xiao-Di Hao; Xiang-Yang Wang; Yuan-Yuan Wu (Bioresource Technology, 2024)

Response of soil aggregate-associated fertility and microbial communities to afforestation in the degraded ecosystem of the Danjiangkou Reservoir, China - Peng Chen; Li Wang; Jun-Ya Li; Wenjie Wan; Run-Qin Zhang; Yi Liu; Zhi-Guo Li (Plant and Soil, 2024)

Integrated framework for geological modeling: integration of data, knowledge, and methods - Hong Li; Bo Wan; Deping Chu; Run Wang; Guoxi Ma; Chuanyang Lei; Shengyong Pan (Bulletin of Engineering Geology and the Environment, 2024)

Comparing combined application of biochar and nitrogen fertilizer in paddy and upland soils: Processes, enhancement strategies, and agricultural implications - Xiaomai Yuan; Xiaoyan Gu; Run Liang; Guichen Ban; Li Ma; Tieguang He; Ziting Wang (Science of The Total Environment, 2024)

Two sex pheromone receptors for sexual communication in the American cockroach - Na Li; Renke Dong; Huanchao Zeng; Yan Zhang; Run Huang; Wei Liu; Fengming Cao; Jincong Yu; Mingtao Liao; Jingyou Chen; Wenlei Zhang; Zejian Huang; et al. (Science China Life Sciences, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Integrative Metabolomics and Whole Transcriptome Sequencing Reveal Role for TREM2 in Metabolism Homeostasis in Alzheimer’s Disease - Meng Wang; Tao Wei; Chaoji Yu; Ruiyang Li; Yunsi Yin; Hanchen Yang; Run Di; Xinyi Xia; Qi Qin; Yi Tang (Molecular Neurobiology, 2024)

Effects of different irrigation amounts and biochar application on soil physical and mechanical properties in the short term - Chuan Zhang; Junan Zhou; Haofang Yan; Muhammad Akhlaq; Yuxin Ni; Run Xue; Jun Li (Irrigation and Drainage, 2024)
Biochar application, as a kind of soil amendment, significantly influences soil physical and mechanical properties. This study revealed the effects of biochar application on the physical and mechanical properties of a clay‐type soil at different irrigation levels. Soil was treated with three levels of biochar application: B0 (0 t ha⁻¹), B1 (25 t ha⁻¹) and B2 (50 t ha⁻¹), and three levels of irrigation: T0 (1.2 pan evaporation E p ), T1 (1.0 E p ) and T2 (0.8 E p ). The results indicated that other treatments reduced the soil bulk density compared with the control treatment (CK) (B0T1). Compared to CK, the highest reduction in soil bulk density was 18%. Irrigation did not improve the soil bulk density and porosity at the same biochar application in the short term. Biochar enhanced the stability of the soil aggregates. Compared to CK, the largest MWD (mean weight diameter) was enhanced by 9%. The addition of biochar and decreasing irrigation could decrease soil cohesion. The addition of biochar and increasing irrigation could increase the soil internal friction angle. The soil cohesion first increased and then decreased as the soil water content increased. According to the fitting formula, the soil cohesion was found to be minimum at B2T2, which was a decrease of 39% compared to B0T1. At the same irrigation level, the soil internal friction angle decreased with increasing soil water content. Soil penetration resistance showed a decreasing trend with the application of biochar. The more irrigation there is, the larger the soil penetration resistance.

Overall and geographic pattern of incidence, fatality and mortality of sepsis among hospitalized non-child cancer patients in China: A nationwide cross-sectional study - Bin Lu; Yang Xu; Na Li; Yueyang Zhou; Xudong Ma; Yan Chen; Run Dong; Xiang Zhou; Min Dai; Hongda Chen; Li Weng; Bin Du (Science Bulletin, 2024)

Bi-2-(2-phenethyl)chromone derivatives from agarwood of Aquilaria filaria in the Philippines - Hong-Run Yang; Hao Wang; Pei Wang; Fang-Zheng Liu; Hong-Xing Chai; Cai-Hong Cai; Li Yang; Jing-Zhe Yuan; Bei Jiang; Wen-Li Mei; Hao-Fu Dai (Phytochemistry, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

microRNA-3037 targeting CYP6CY2 confers imidacloprid resistance to Sitobion miscanthi (Takahashi) - Bai-Zhong Zhang; Yu-Tai Jiang; Ling-Ling Cui; Gui-Lei Hu; Xin-An Li; Pei Zhang; Xiang Ji; Ping-Chuan Ma; Fan-Bin Kong; Run-Qiang Liu (Pesticide Biochemistry and Physiology, 2024)

Research on the equivalent stiffness of bucket foundations for offshore wind power - Huishan Li; Jijian Lian; Run Liu; Haijun Wang; Xu Yang (Ocean Engineering, 2024)

Seasonal predictability of SST anomalies and marine heatwaves over the Kuroshio extension region in the Copernicus C3S models - Chenguang Zhou; Hong-Li Ren; Yu Geng; Run Wang; Lin Wang (Ocean Modelling, 2024)

Sustainable and efficient scouring/bleaching strategy for cotton fabric using sucrose octaacetate/peroxide activated system: Mechanistic insights, performance optimizations, and environmental benefits - Huiyu Jiang; Run Lu; Xin Xiao; Yan Liang; Jie Chen; Qing Li; Wen Zhang (Journal of Cleaner Production, 2024)

Sodium l-glutamate improves the lyophilization survival rate of Lactiplantibacillus plantarum L5 by regulating cellular pyruvate - Run Zhou; Yuwei Wu; Ying Li; Longyan Li; Jialin Wu; Xinqiang Xie; Huishu Huang; He Gao; Lei Wu; Hui Zhao; Moutong Chen; Qingping Wu (Food Bioscience, 2024)

Multi-objective optimization for generative morphological design using energy and comfort models with a practical design of new rural community in China - Run Li; Linxi Luo; Xiangfeng Li; Jiyuan Wu; Feifeng Jiang; Wei Wang (Energy and Buildings, 2024)

Stratigraphic evidence for a major unconformity within the Ediacaran System - Run Li; Xiqiang Zhou; Michael P. Eddy; Ryan B. Ickert; Zhenfei Wang; Dongjie Tang; Kang-Jun Huang; Peng Peng (Earth and Planetary Science Letters, 2024)

A Four Amino Acid Metabolism-Associated Genes (AMGs) Signature for Predicting Overall Survival Outcomes and Immunotherapeutic Efficacy in Hepatocellular Carcinoma - Lu-sheng Liao; Zi-jun Xiao; Jun-li Wang; Ting-jun Liu; Feng-die Huang; Yan-ping Zhong; Xin Zhang; Ke-heng Chen; Run-lei Du; Ming-you Dong (Biochemical Genetics, 2024)

A novel stress concentration inspection method for marine oil and gas pipeline based on UNSM - Jiaxing Xin; Jinzhong Chen; Renyang He; Rui Li; Xiaolong Li; Chang Liu; Run-kun Lu; Zhengda Su; Wenbo Han (Ocean Engineering, 2024)

Calculation method for the ultimate torsional capacity of bucket foundations in clay - Qingxin Li; Run Liu; Xiaolei Wang; Jijian Lian; Guangsi Chen (Ocean Engineering, 2024)

Modeling hydraulic conductivity function of frozen soil - Xiao-kang Li; Xu Li; Xiang-sheng Chen; Run-ze Tian; Shuang-fei Zheng (Journal of Hydrology, 2024)

Reshaped buried interface by comprehensive passivation for highly efficient perovskite photovoltaics - Lei Huang; Kai-Li Wang; Run-Jun Jin; Jing Chen; Chun-Hao Chen; Yu Xia; Yan-Hui Lou; Zhao-Kui Wang (Chemical Engineering Journal, 2024)

Identification, distribution, bactericidal and immunoregulatory activities of NK-lysins in grass carp (Ctenopharyngodon idella) - Gai Ling Wang; En Zhong Li; Da Hong Li; Ming Cheng Wang; Shan Shan Sun; Run Yan Xiong; Chuan Feng Li; Bao Jian Sun; Hai Xia Xie (Aquaculture, 2024)

Preparing a heavy-metal adsorbent based on alginate-like extracellular polymers from conventional activated sludge via polyethyleneimine grafting - Chen Shi; Run-Gen Zeng; Shi-Chao Yuan; Lin Zhang; Xiang-Yang Wang; Li-Ting Hao; Xiao-Di Hao; Nan Zhang; Yuan-Yuan Wu (Sustainable Chemistry and Pharmacy, 2024)

The association between artificial light at night and gestational diabetes mellitus: A prospective cohort study from China - Junhao Liao; Chuan Yu; Jiarui Cai; Run Tian; Xingyue Li; Hong Wang; Lin Li; Guishuang Song; Leyao Fu; Xinxi Li; Qiaoyue Ge; Ling Zhang; et al. (Science of The Total Environment, 2024)

Marine nitrogen cycling in the aftermath of the Marinoan Snowball Earth - Yawen Lu; Run Li; Zhenfei Wang; Zekun Meng; Xiqiang Zhou; Chao Chang; Xingliang Zhang; Kang-Jun Huang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Engine-out emissions from an ammonia/diesel dual-fuel engine – The characteristics of nitro-compounds and GHG emissions - Run Chen; Tie Li; Xinran Wang; Shuai Huang; Xinyi Zhou; Shiyan Li; Ping Yi (Fuel, 2024)

Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Long-term exposure to reduced specific-size ambient particulate matter and progression of arterial stiffness among Chinese adults - Dankang Li; Shouling Wu; Linxi Tang; Shuohua Chen; Feipeng Cui; Yudiyang Ma; Run Liu; Jianing Wang; Yaohua Tian (Journal of Hazardous Materials, 2024)

Residential greenness and incident idiopathic pulmonary fibrosis: A prospective study - Linxi Tang; Feipeng Cui; Yudiyang Ma; Dankang Li; Jianing Wang; Run Liu; Yaohua Tian (Environmental Research, 2024)

3D microprinting of QR-code integrated hydrogel tactile sensor for real-time E-healthcare - Zi-Rong Li; Tian-Run Lv; Zhenxu Yang; Wen-Hai Zhang; Ming-Jie Yin; Ken-Tye Yong; Quan-Fu An (Chemical Engineering Journal, 2024)

Insights into the heteroatom-incorporated storage mechanism of hierarchically interconnected porous conjugated polymer networks for extremely stable potassium-ion storage - Yingxv Gao; Qunbo Hui; Qi Liu; Xiaohong Xia; Run Li; Yuxi Chen; Deping Wang; Hongbo Liu (Chemical Engineering Journal, 2024)

Study on indoor thermal perception, behavioral adaptation in late pregnancy and their effects on adverse birth outcomes in south China - Jie Ni; Huailin Wang; Xinyue Yu; Run Gao; Yanqiu Li; Zhaosong Fang; Jason Kai Wei Lee; Zhenghong Zhu; Maimaitiminjiang Wulayin; Xin Chen; Cunrui Huang; Qiong Wang (Building and Environment, 2024)

Impacts of compound extreme weather events on summer ozone in the Beijing-Tianjin-Hebei region - Peilan Lu; Run Liu; Zheng Luo; Shiyi Li; Yanxing Wu; Wenzhao Hu; Xin Xue (Atmospheric Pollution Research, 2024)

Distinct North American teleconnection of the strong El Niños as modulated by the ENSO-annual cycle combination mode - Minghong Liu; Hong-Li Ren; Fang Zhou; Run Wang (Climate Dynamics, 2024)

The antimicrobial effect and mechanism of the Artemisia argyi essential oil against bacteria and fungus - Daoyuan Li; Run Wang; Meng You; Naidong Chen; Li Sun; Naifu Chen (Brazilian Journal of Microbiology, 2024)

Recent developments on the removal of zinc from electric arc furnace dust by using microwave heating - Yuandong Xiong; Kai Wang; Dejin Qiu; Mamdouh Omran; Run Huang; Ying Li; Shiyu Wei; Inam Ullah Khan; Dengwei Zhang; Abdallah Ahmed; Yaowei Yu (Environmental Science and Pollution Research, 2024)

Transcriptomic analysis of ncRNAs and mRNAs interactions during drought stress in switchgrass - Cong Guan; Wei Li; Guoliang Wang; Ruimei Yang; Jinglei Zhang; Jinhong Zhang; Bo Wu; Run Gao; Chunlin Jia (Plant Science, 2024)

Activated carbon-boosted BiOI in CO2 adsorption and electron transfer for photothermally catalyzed CO2 oxidative dehydrogenation of propane - Run-Qing Miao; Zhen-Hong He; Bao-Ting Wu; Jiajie Liu; Sen-Wang Wang; Kuan Wang; Weitao Wang; Lu Li; Zhao-Tie Liu (Chemical Engineering Journal, 2024)

Physicochemical properties of clayey deposits slurry treated by lime-activated ISSA and GGBS considering seawater salinity effect - Zhao Sun; Wen-Bo Chen; Run-Dong Zhao; Jiang-Shan Li; Zhen-Yu Yin; Jian-Hua Yin; Yong-Gui Chen (Applied Clay Science, 2024)

Spatial-temporal variation of soil organic matter decomposition potential in China - Qi Chen; Zeyan Zhou; Sulin Cai; Meiqi Lv; Yinghui Yang; Yunchao Luo; Han Jiang; Run Liu; Tingting Cao; Bei Yao; Yunru Chen; Qiang Li; et al. (Soil and Tillage Research, 2024)

Fluctuations of Qiangyong glacier in southern Tibetan Plateau over the past 500 years recorded by proglacial lacustrine sediments - Run Zhang; Qi Feng; Fei Zhang; Le Li; Yang Xu; Zhangdong Jin (Quaternary International, 2024)

Outdoor artificial light at night and male sperm quality: A retrospective cohort study in China - Run Tian; Tingting Yang; Chenghan Xiao; Fuping Li; Leyao Fu; Lu Zhang; Jiarui Cai; Sixuan Zeng; Junhao Liao; Guishuang Song; Chuan Yu; Ben Zhang; et al. (Environmental Pollution, 2024)

Green N1 additive modified perovskite precursor enables effective manufacturing of large-area solar cell modules with high efficiency and stability - Yue Zang; Yibo Tu; Chuanjia Jiao; Wangnan Li; Peng Zhou; Jiahao Cheng; Gaoyuan Yang; Tianxiang Shao; Jingchuan Ye; Guodong Li; Liang Chu; Shaojian Lu; et al. (Chemical Engineering Journal, 2024)

Transient Performance of Gas-Engine-Based Power System on Ships: An Overview of Modeling, Optimization, and Applications - Shen Wu; Tie Li; Run Chen; Shuai Huang; Fuguo Xu; Bin Wang (Journal of Marine Science and Engineering, 2023)
Liquefied natural gas (LNG) is widely regarded as the midterm solution toward zero-carbon transportation at sea. However, further applications of gas engines are challenging due to their weak dynamic load performance. Therefore, the comprehension of and improvements in the dynamic performance of gas-engine-based power systems are necessary and urgent. A detailed review of research on mechanisms, modeling, and optimization is indispensable to summarize current studies and solutions. Developments in engine air-path systems and power system load control have been summarized and compared. Mechanism studies and modeling methods for engine dynamic performance were investigated and concluded considering the trade-off between precision and simulation cost. Beyond existing studies, this review provides insights into the challenges and potential pathways for future applications in decarbonization and energy diversification. For further utilization of clean fuels, like ammonia and hydrogen, the need for advanced air–fuel ratio control becomes apparent. These measures should be grounded in a deep understanding of current gas engines and the combustion characteristics of new fuels. Additionally, the inherent low inertia feature of electric power systems, and consequently the weak dynamic performance when adopting renewable energies, must be considered and studied to ensure system reliability and safety during transient conditions.

Effects of Ulva prolifera Degradation on Growth Performance and Antioxidant Capacity of Japanese Flounder (Paralichthys olivaceus) Family - Yingming Yang; Wenlong Li; Run Wang; Dan Xu; Yadong Chen; Zhongkai Cui; Songlin Chen (Fishes, 2023)
Massive macroalgae blooms, primarily caused by the overgrowth of Ulva prolifera (U. prolifera) in the Yellow Sea of China, pose a severe risk to both marine organisms and the aquaculture industry. This study’s aim was to evaluate the impact of U. prolifera degradation on the growth performance and antioxidant capacity of Japanese flounder (Paralichthys olivaceus) and select some potential Japanese flounder families (labeled 2101–2108, established by crossbreeding) tolerating U. prolifera degradation conditions. Thus, a 60-day U. prolifera exposure experiment was conducted. The results showed that the contents of Na, K, Mg, and Fe elements in the U. prolifera degradation water were significantly increased. The specific growth rate and survival rate of flounder were significantly decreased under the U. prolifera degradation condition, while the 2101 and 2103 flounder families showed a better growth performance compared with the positive control (PC) group. Moreover, the results showed that activities of total antioxidant capacity (T-AOC), transaminases, and alkaline phosphatase (AKP) in serum were significantly decreased, while the 2103 flounder family showed higher activities. Furthermore, U. prolifera degradation significantly increased superoxide dismutase (SOD) activity and glutathione (GSH) content while decreasing catalase (CAT) activity and malondialdehyde (MDA) content in the liver. Specifically, SOD and CAT activities of the 2103 flounder family were higher than the 2101 flounder family and PC group. In addition, the gill SOD and CAT activities of the 2103 flounder family were significantly higher than the PC group. Similarly, the antioxidant-related gene (sod and cat) expressions were synchronously upregulated or downregulated in the liver and gills in response to U. prolifera degradation. These results revealed that U. prolifera degradation decreased the growth performance and influenced the antioxidant capacity of Japanese flounder, while the 2103 flounder family had better advantages in the U. prolifera degradation condition. Therefore, the 2103 flounder family could be regarded as the potential flounder family tolerating U. prolifera degradation. The increased Fe content in the U. prolifera degradation water may be one of the main causes of the physiological alterations observed in Japanese flounder.

Study on the dynamic embedment variation of shallow embedded submarine pipelines in sand - Zheng Yu; Run Liu; Chengfeng Li; Xintong Hao (Ocean Engineering, 2023)

A review of alginate-like extracellular polymers from excess sludge: Extraction, characterization, and potential application - Run-Gen Zeng; Chen Shi; Li-Ting Hao; Ao Huang; Tian Yuan; Nan Zhang (Journal of Water Process Engineering, 2023)

Graphene oxide composited with different size of organic molecules for hydrogen isotopic water separation in membrane distillation - Run Li; Denggao Guan; Min Chen; Xin Zhang; Haowei Yang; Cigang Xu (Journal of Environmental Chemical Engineering, 2023)

A novel non-centrifugal sugar prepared from tiger nut (Cyperus esculentus L.) meal: Preparation methods and comparison with sugarcane - Run-Yang Zhang; Xin-Yun Huang; Peng-Xiao Chen; Tian Li; Meng-Meng Jiang; Yi-Long Wang; Wen-Xue Zhu; Hua-Min Liu (Food Research International, 2023)

The role of the gut-liver axis in modulating non-alcoholic fatty liver disease through dietary patterns and microecological agents - Yucheng Fang; Ziyang Fang; Ziwei Li; Run Yu; Haimeng Zhang; Qinwen Wang; Xiangrong Cheng; Guowei Le; Guoqing Wu (Food Bioscience, 2023)

Distributed bending stiffness estimation of bridges using adaptive inverse unit load method - Run-Zhou You; Ting-Hua Yi; Liang Ren; Hong-Nan Li (Engineering Structures, 2023)

Theoretical and Numerical Studies on the Coupling Deformation of Global Lateral Buckling and Walking of Submarine Pipeline - Run Liu; Xintong Hao; Chengfeng Li; Qingxin Li; Zheng Yu; Dang Zhao (Journal of Ocean University of China, 2023)

Comparative study on ventilation and air conditioning system schemes based on virus pollution control in hospital infusion room - Weixue Cao; Xudong Zhang; Wanxiang Yao; Run Sun; Yutong Du; Quanbin Shi; Zipeng Li (Aerobiologia, 2023)

Biodegradation mechanism of chlortetracycline by a novel fungal Aspergillus sp. LS-1 - Wenshan He; Run Jiang; Siqi Li; Minglu Zhang; Tingting Zhang; Xiaobiao Zhu; Xiaohui Wang (Chemosphere, 2023)

Soil aggregate-associated organic carbon mineralization and its driving factors in rhizosphere soil - Jun-Ya Li; Peng Chen; Zhi-Guo Li; Lin-Yang Li; Run-Qin Zhang; Wei Hu; Yi Liu (Soil Biology and Biochemistry, 2023)

The way to elastic ferroelectrics - Ben-Lin Hu; Brahim Dkhil; Run-Wei Li (Science Bulletin, 2023)

Dust effects on mixed-phase clouds and precipitation during a super dust storm over northern China - Run Luo; Yuzhi Liu; Min Luo; Dan Li; Ziyuan Tan; Tianbin Shao; Khan Alam (Atmospheric Environment, 2023)

Exploring adequate CO2 elevation for optimum tomato growth and yield under protected cultivation - Muhammad Akhlaq; Zhang Chuan; Yan Haofang; Liang Shaowei; Yuxin Ni; Junan Zhou; Run Xue; Jun Li; Zawar Hussain; Shahzad Iqbal (Journal of Plant Physiology, 2023)

Manual correction of genome annotation improved alternative splicing identification of Artemisia annua - Zhaoyu Liu; Yupeng Du; Zhihao Sun; Bohan Cheng; Zenghao Bi; Zhicheng Yao; Yuting Liang; Huiling Zhang; Run Yao; Shen Kang; Yuhua Shi; Huihua Wan; et al. (Planta, 2023)

The Effects of Wave-Induced Stokes Drift and Mixing Induced by Nonbreaking Surface Waves on the Ocean in a Climate System Ocean Model - Peng Fan; Jiangbo Jin; Run Guo; Guixian Li; Guangqing Zhou (Journal of Marine Science and Engineering, 2023)
Oceanic general circulation models (OGCMs) are important tools used to investigate mechanisms for ocean climate variability and predict the ocean change in the future. However, in most current ocean models, the impact of sea surface waves as one of the most significant dynamic processes in the upper ocean is absent. In this study, the Stokes drift and the vertical mixing induced by nonbreaking surface waves derived from the wave model (WAVEWATCH III) are incorporated into a Climate System Ocean Model, and their effects on an ocean climate simulation are analyzed. Numerical experiments show that both physical processes can improve the simulation of sea surface temperature (SST) and mixed layer depth (MLD) in the Southern Hemisphere. The introduction of Stokes drift effectively reduces the subsurface warm bias in the equatorial tropics, which is caused by the weakening of vertical mixing in the equatorial region. The nonbreaking surface wave mainly reduces the temperature bias in the Southern Ocean by enhancing mixing in the upper ocean. For the MLD, the Stokes drift mainly improves the simulation of the winter MLD, and the nonbreaking surface wave improves the summer MLD. For MLD south of 40° S in summer, the introduction of nonbreaking surface waves resulted in a reduction of 11.86 m in MLD bias and 7.8 m in root mean square errors (RMSEs), respectively. For winter subtropical MLD in the Southern Hemisphere, considering the Stokes drift, the MLD bias and RMSEs were reduced by 2.49 and 5.39 m, respectively. Adding these two physical processes simultaneously provides the best simulation performance for the structure of the upper layer. The introduction of sea surface waves effectively modulates the vertical mixing of the upper ocean and then improves the simulation of the MLD. Thus, sea surface waves are very important for ocean simulation, so we will further couple a sea waves model in the Chinese Academy of Sciences Earth System Model (CAS-ESM) as part of their default model component.

Cytotoxic lanostane-type triterpenes from the fruiting bodies of Ganoderma lucidum - Xiu-run Huang; Fang Cai; Jing Chen; Chang-hui Wu; Ye Li; Jian-hua Xu; Peng Li (Natural Product Research, 2023)

Evaluation and uncertainty analysis of Himawari-8 hourly aerosol product version 3.1 and its influence on surface solar radiation before and during the COVID-19 outbreak - Chenqian Tang; Chong Shi; Husi Letu; Run Ma; Mayumi Yoshida; Maki Kikuchi; Jian Xu; Nan Li; Mengjie Zhao; Liangfu Chen; Guangyu Shi (Science of The Total Environment, 2023)

Suppression effects and mechanisms of three typical solid suppressants on titanium hydride dust explosions - Shi-zhou Li; Yang-fan Cheng; Rui Wang; Meng Li; Run Li; Hong-hao Ma (Process Safety and Environmental Protection, 2023)

Electronic modulation and surface reconstruction on heterostructured CoP-Ni2P nanosheets with phosphate-rich surface for synergistically triggering oxygen evolution reaction - Fei Nie; Xueli Yin; Yihua Cao; Zhi Li; Xiaoping Dai; Weiyu Song; Yujie Liu; Yonghao Gan; Ying Ye; Run Cai; Xin Zhang (Fuel, 2023)

Identification, quantitative and bioactivity analyses of aroma and alcohol-soluble components in flowers of Gardenia jasminoides and its variety during different drying processes - Run Yu; Yue Li; Dun Si; Shulei Yan; Jingjing Liu; Jinping Si; Xinfeng Zhang (Food Chemistry, 2023)

Continuous Co-incorporation of Chinese Milk Vetch and Rice Straw with Reduced Chemical Fertilizer Maintains Rice Yield as a Consequence of Increased Carbon and Nitrogen Storage in Soil Aggregates - Rongyan Bu; Wenlong Cheng; Shang Han; Run Hu; Hui Wang; Shan Tang; Min Li; Qin Zhu; Ji Wu; Weidong Cao (Journal of Soil Science and Plant Nutrition, 2023)

DEM investigation of the mechanical behavior of frozen soil along various stress paths - Ruohan Sun; Run Liu; Huan Zhang; Chun Liu; Chengfeng Li (Bulletin of Engineering Geology and the Environment, 2023)

Composites of TiO2 pillared sericite: Synthesis, characterization and photocatalytic degradation of methyl orange - Yu Liang; Wei Li; Baohui Bei; Chong Li; Zetian He; Xuan Wang; Run Zhou; Hao Ding; Shu Li (Applied Clay Science, 2023)

Bed level changes in the surf zone during post-storm beach recovery - Pengpeng Hu; Zhiqiang Li; Chunhua Zeng; Daoheng Zhu; Run Liu; Qianxin Su; Jieping Tang; Yamin Zhu (Frontiers in Marine Science, 2023)
The study of post-storm beach recovery is important for economic development and the protection of life in coastal areas. In this study, field observations were conducted for 21 days in the surf zone of Dongdao Beach, Hailing Island, China, after tropical storm “Cempaka”. Data on depth, wave, Eulerian velocity, sediment, three-dimensional topography of the beach, and high-frequency variations in bed-level elevation were collected. The results showed that the beach experienced medium- to low- to medium-energy waves during field observations and covered two complete astronomical tide cycles. Contrary to the effect of wave energy conditions on beaches under normal wave conditions, a higher wave energy during beach recovery can promote silting and accelerate beach recovery. Tidal water level is an important factor affecting beach restoration, and a smaller tidal range is conducive to beach accretion. In a mixed semidiurnal tide, beach erosion and accretion occurred in the “highest tide” and “sub-highest tide” tidal cycles, respectively, and the combined effect of the two affected the change in the bed level in a mixed semidiurnal tide. After the storm, the hydrodynamic forcing mechanism and self-organization process of the sand bar jointly drove the formation of the topography of the bar channel in the surf zone. After the storm stopped, the spectral energy in free surface elevation was mainly distributed in the very low frequency and decayed rapidly at the infragravity band. The very low-frequency pulsation of the surf zone during recovery is a prominent feature of bed-level elevation, depth, and velocity. This study provides a good case for the study of hydrodynamic and bed level changes in the post-storm surf zone, as well as a reference for future studies of the intrinsic mechanisms post-storm beach recovery processes around the world.

A Modulation Recognition System for Underwater Acoustic Communication Signals Based on Higher-Order Cumulants and Deep Learning - Run Zhang; Chengbing He; Lianyou Jing; Chaopeng Zhou; Chao Long; Jiachao Li (Journal of Marine Science and Engineering, 2023)
Underwater acoustic channels, influenced by time-varying, space-varying, frequency-varying, and multipath effects, pose significant interference challenges to underwater acoustic communication (UWAC) signals, especially in non-cooperative scenarios. The task of modulating and identifying distorted signals faces huge challenges. Although traditional modulation recognition methods can be useful in the radio field, they often prove inadequate in underwater environments. This paper introduces a modulation recognition system for recognizing UWAC signals based on higher-order cumulants and deep learning. The system achieves blind recognition of received UWAC signals even under non-cooperative conditions. Higher-order cumulants are employed due to their excellent noise resistance, enabling the differentiation of OFDM signals from PSK and FSK signals. Additionally, the high-order spectra differences among signals are utilized for the intra-class recognition of PSK and FSK signals. Both simulation and lake test results substantiate the effectiveness of the proposed method.

Micro-mechanism insights into the adsorption of anionic dyes using quaternary ammonium-functionalised chitosan aerogels - Nan Du; Li-Yuan Huang; Yan-Shu Xiong; Run Tian; Jiang-Yu Yin; Dan-Yu Cao; Dong-Bin Hu; Hai-Qin Lu; Wen Li; Kai Li (Carbohydrate Polymers, 2023)

Characteristics and a mechanism of dust weather in Northern China - Tianbin Shao; Yuzhi Liu; Ziyuan Tan; Dan Li; Min Luo; Run Luo (Climate Dynamics, 2023)

Evolutionary research trend of Polygonatum species: a comprehensive account of their transformation from traditional medicines to functional foods - Xiao-Li Li; Run-Hui Ma; Fan Zhang; Zhi-Jing Ni; Kiran Thakur; Shaoyun Wang; Jian-Guo Zhang; Zhao-Jun Wei (Critical Reviews in Food Science and Nutrition, 2023)

Air pollution, alcohol consumption, and the risk of elevated liver enzyme levels: a cross-sectional study in the UK Biobank - Run Liu; Dankang Li; Junqing Xie; Lulin Wang; Yonghua Hu; Yaohua Tian (Environmental Science and Pollution Research, 2023)

Nano-Fe promotes accumulation of phytoestrogens and volatile compounds in Trifolium pratense flowers - Yitong Li; Run Li; Xiaoyan Ren; Tian Wang; Haitao Yu; Quan Liu (Theoretical and Experimental Plant Physiology, 2023)

A new butenolide with antifungal activity from solid co-cultivation of Irpex lacteus and Nigrospora oryzae - Ya-Mei Wu; Xue-Qiong Yang; Jing-Xin Chen; Ting Wang; Tai-Ran Li; Fan-Rong Liao; Run-Tong Liu; Ya-Bin Yang; Zhong-Tao Ding (Natural Product Research, 2023)

Antimicrobial resistome during the transition from an integrated to a monoculture aquaculture farm in southern China - Jin-Tao Yang; Dan-Yu Xiao; Li-Juan Zhang; Hai-Xin Chen; Xing-Run Zheng; Xiao-Li Xu; Hong-Xia Jiang (Science of The Total Environment, 2023)

Enhanced self-sintering mechanical strength of carbon blocks via removal of light molecular-weight compound in green petroleum coke - Jiao Tan; Ping Liu; Pei Gong; Yanli Liu; Jian Chen; Run Li; Chuanjun Tu (Fuel, 2023)

Projected change of East-Asian winter precipitation related to strong El Niño under the future emission scenarios - Yu Huang; Hong-Li Ren; Jong-Seong Kug; Run Wang; Jingxin Li (Climatic Change, 2023)

A seasonal circulation index for the ocean and its application to the South China Sea - Qiang Li; Run Xin Huang; Lingling Xie (Frontiers in Marine Science, 2023)
Ocean circulation is crucial in redistributing mass and energy on Earth. However, it varies significantly on a seasonal time scale due to external forcing. To quantify the seasonality of ocean circulation, we propose a seasonal circulation index ( SCI ). This index is defined as the normalized maximum deviation from the velocity vector, whose magnitude is the largest in one period. We have substantiated the efficiency of this index using the monsoon wind in the South China Sea (SCS). By utilizing this index, we have obtained the 3D structure of the seasonality of ocean circulation in the SCS. The SCI and the seasonal circulation amplitude ( SCA ) exhibit large values over 0.9 and 0.8 m s -1 in the western boundary current. Alternating southwest-northeastward bands of SCI with high and low values are distributed from the north shelf to the south, especially in the eastern basin. Although SCA decreases significantly with depth, SCI exhibits values higher than 0.7 in both the middle and deep layers, indicating a noteworthy seasonality and middle-layer enhancement in the abyssal basin of the SCS.

Overexpression of OsNF-YB4 leads to flowering early, improving photosynthesis and better grain yield in hybrid rice - Meifang Peng; Feng Gan; Xiaomin Lin; Run Yang; Shaoyi Li; Wei Li; Lan Wu; Xiaoli Fan; Kegui Chen (Plant Science, 2023)

Porous ceramic membranes from coal fly ash with addition of various pore-forming agents for oil-in-water emulsion separation - Jiguang Huang; Haiping Chen; Run Qi; Jihao Yang; Zhaohao Li; Heng Zhang (Journal of Environmental Chemical Engineering, 2023)

Association between nitrogen dioxide concentration and hypertension hospitalization: A multicenter time-series analysis in Xinxiang, China - Shi-qi Ge; Yong-bin Wang; Fei Lin; Run-ran Miao; Kai Zhang; Li Li; Hui-ge Guo; Qian Wang; Li Zhang; Zhi-gang Chen; Guo-an Zhao (Atmospheric Pollution Research, 2023)

Deficiency of Lactoferrin aggravates lipopolysaccharide-induced acute inflammation via recruitment macrophage in mice - Can Liu; Qiu Peng; Lingyu Wei; Zhengshuo Li; Xiaoyue Zhang; Yangge Wu; Jia Wang; Xiang Zheng; Yuqing Wen; Run Zheng; Qun Yan; Qiurong Ye; et al. (BioMetals, 2023)

LC-MS Based Metabolomic Profiling of Largehead Hairtail (Trichiurus japonicus) Ovary Reveals Metabolic Signatures of Ovarian Developmental Process (II–IV) - Liu-Ying Feng; Li-Ping Yan; Run-Wei Li; Sheng-Fa Li; Jia-Hua Cheng; Yan Jin (Fishes, 2023)
Trichiurus japonicus is an economically important fish that ranks 11th in global marine fish capture production. However, the reproductive characteristics of this fish have undergone notable changes in recent decades, potentially affecting the quality of offspring and sustainable utilization. To improve our understanding of the physiological regulation of maturation in T. japonicus, untargeted liquid chromatography mass spectrometry was utilized to identify the small molecules that characterize the comprehensive metabolic profiles of ovaries during ovary development from stage II to stage IV. According to the results of OPLS-DA, the ovarian metabolite profiles of the three developmental stages were separated. The concentrations of 124 and 100 metabolites were significantly altered between stage II vs. III and III vs. IV, respectively. Lipids and lipid-like molecules accounted for the largest proportion of the altered metabolites, followed by amino acids, peptides, and analogues. The significantly altered metabolites-enriched pathways differed slightly between stages II and III and stages III and IV. Steroid-related pathways were heavily affected during stages II to III, while significantly altered metabolites from stages III to IV were involved in oocyte-maturation-related pathways. Through metabonomics analysis, potentially important metabolic pathways and metabolites between different ovarian stages were detected, providing basic information for further investigation of maturation mechanisms in wild fish.

Failure mechanism of a large-scale composite deposits caused by the water level increases - Xin Zhang; Guo-xiang Tu; Qi-feng Luo; Hao Tang; Yu-lin Zhang; An-run Li (Journal of Mountain Science, 2023)

Peracetic acid activation via the synergic effect of Co and Fe in CoFe-LDH for efficient degradation of pharmaceuticals in hospital wastewater - Zhi-Hui Xie; Chuan-Shu He; Yong-Li He; Shu-Run Yang; Si-Ying Yu; Zhaokun Xiong; Ye Du; Yang Liu; Zhi-Cheng Pan; Gang Yao; Bo Lai (Water Research, 2023)

Extracting compositional blocks of alginate-like extracellular polymers (ALE) from conventional activated sludge (CAS) - Chen Shi; Run-Gen Zeng; Li-Ting Hao; Xiao-Di Hao; Ji Li (Science of The Total Environment, 2023)

A crack characterization model for subsea pipeline based on spatial magnetic signals features - Jiaxing Xin; Rui Li; Jinzhong Chen; Run-kun Lu; Chang Liu; Zhengda Su; Renyang He; Hongwu Zhu (Ocean Engineering, 2023)

Preparation of mixed matrix membranes by layered double hydroxides of amino acid intercalation and Pebax for ameliorated CO2 separation - Hui Guo; Shaohan Lian; Run Li; Yijuan Zhang; Quan Zhao; Chunfeng Song (Journal of Environmental Chemical Engineering, 2023)

Strain-induced conductive network and memory effect of maximum strain in liquid metal hierarchical structure - Shengding Wang; Fali Li; Shiying Li; Jinwei Cao; Shengbin Li; Zidong He; Huiyun Xiao; Yuanzhao Wu; Jie Shang; Yiwei Liu; Run-Wei Li (Chemical Engineering Journal, 2023)

Valorization of lignin through reductive catalytic fractionation of fermented corn stover residues - Wen-Zheng Yin; Ling-Ping Xiao; Shuang-Lin Zou; Wen-Xin Li; Hongliang Wang; Run-Cang Sun (Bioresource Technology, 2023)

How much urban air quality is affected by local emissions: A unique case study from a megacity in the Pearl River Delta, China - Meng-Xue Tang; Xiao-Feng Huang; Pei-Ting Yao; Run-Hua Wang; Zhi-Jie Li; Chao-Xi Liang; Xing Peng; Li-Ming Cao; Ke Du; Kuangyou Yu; Song Guo (Atmospheric Environment, 2023)

Research on the Critical Buckling Pressure of Bucket Foundations with Inner Compartments for Offshore Wind Turbines - Guodong Sun; Run Liu; Qingxin Li; Guoyu Huang; Zhenbo Zhou; Cheng Zhang (Journal of Ocean University of China, 2023)

Variations in the concentration, source and flux of polycyclic aromatic hydrocarbons in sediments of the Pearl River Estuary: Implications for anthropogenic impacts - Yali Li; Nairong Guo; Ke Yuan; Baowei Chen; Junjie Wang; Maofeng Hua; Jing Yu; Jingyan Hu; Run Lu; Shichun Zou; Ying Yang (Science of The Total Environment, 2023)

Energy, economic and environment assessment of membrane-cryogenic hybrid recovery propane process — Process simulation and life cycle assessment - Zezhou Zhang; Run Li; Shaohan Lian; Ziyou Jiang; Qingling Liu; Chunfeng Song (Journal of Cleaner Production, 2023)

Liraglutide inhibits AngII-induced cardiac fibroblast proliferation and ECM deposition through regulating miR-21/PTEN/PI3K pathway - Jun Wang; Run Guo; Xiaoli Ma; Ying Wang; Qianyu Zhang; Nan Zheng; Jun Zhang; Chenchen Li (Cell and Tissue Banking, 2023)

Biotransformation of sulfamonomethoxine in a granular sludge system: Pathways and mechanisms - Meng-Yuan Li; Run-Dong Zhang; Yi-Xing Lin; Qi-Wen Li; Qiu-Yue Zhao; Zong-Xi Zhao; Zhong-Ming Ling; Long-Fei Shu; Min Zhang; Li-Xin Hu; Yi-Jing Shi; Guang-Guo Ying (Chemosphere, 2023)

Emission characteristics, risk assessment and scale effective control of VOCs from automobile repair industry in Beijing - Hailin Wang; Run Hao; Xiaoqi Xie; Guoao Li; Xinxin Wang; Wenqing Wu; Huan Zhao; Zhongshen Zhang; Li Fang; Zhengping Hao (Science of The Total Environment, 2023)

Reducing light exposure enhances the circadian rhythm of the biological clock through interactions with the gut microbiota - Yu Zhang; Yong Li; Yilin Yuan; Jun Wang; Shiyu Zhang; Run Zhu; Yan Wang; Yinbao Wu; Xindi Liao; Jiandui Mi (Science of The Total Environment, 2023)

Damming has changed the migration process of microplastics and increased the pollution risk in the reservoirs in the Shaying River Basin - Jiachen Shen; Xu Gu; Run Liu; Hongyu Feng; Dianpeng Li; Yan Liu; Xufei Jiang; Ge Qin; Shuqing An; Ning Li; Xin Leng (Journal of Hazardous Materials, 2023)

Comparative analysis of cold-responsive genes under short-term cold stimulation and cold-adaptive genes under long-term heterogeneous environments reveals a cold adaptation mechanism in weeping forsythia - Yong Li; Shu-Chen Wang; Qian Li; Ming-Wan Li; Run-Li Mao; He-Chen Zhang; Wang-Jun Yuan; Jine Quan (Genetica, 2023)

Urinary trihalomethane concentrations and liver function indicators: a cross-sectional study in China - Li Yang; Limei Chen; Yamei Hao; Run Zhou; Jingying Zhu; Xun Zhu; Qianqian Wang; Xiuzhu Li; Xinliang Ding; Yanhua Qian (Environmental Science and Pollution Research, 2023)

Hierarchical porous nanosilica derived from coal gasification fly ash with excellent CO2 adsorption performance - Yanfang Liu; Zhiqiang Wang; Wenhui Zhao; Jili Hou; Longpeng Cui; Liang Zou; Chenghao Li; Hongwei Li; Yu Wu; Run Xu; Yongfa Zhu (Chemical Engineering Journal, 2023)

Non-destructive characterization of proton diffusion coefficient within live electroactive biofilm - Linbin Hu; Run Liu; Yang Yang; Qian Fu; Liang Zhang; Xun Zhu; Qiang Liao; Jun Li (Chemical Engineering Journal, 2023)

Sensitivity analysis of heat transfer coefficient in primary system for LMSR core power control system based on Sobol’s method - Lehua Liang; Chuhao Li; Linna Wang; Xuejian Wang; Wenjie Zeng; Run Luo (Annals of Nuclear Energy, 2023)

Comparative assessment of nitrogen fixation rate by 15N2 tracer assays in the South China Sea - Danyang Li; Minfang Zheng; Yusheng Qiu; Limin Lai; Nengwang Chen; Hongmei Jing; Run Zhang; Min Chen (Acta Oceanologica Sinica, 2023)

Nitrate isotope dynamics in the lower euphotic-upper mesopelagic zones of the western South China Sea - Zixuan Li; Chao Xu; Minfang Zheng; Mengya Chen; Yusheng Qiu; Hantao Zhou; Min Chen; Run Zhang (Acta Oceanologica Sinica, 2023)

Binding characteristics of Pb and Zn to low-temperature feces-based biochar-derived DOM revealed by EEM-PARAFAC combined with general and moving-window two-dimensional correlation analyses - Changjun He; Xuwen He; Run Yuan; Na Li; Jinyuan Jiang (Environmental Science and Pollution Research, 2022)

Evolution mechanism and deformation stability analysis of rock slope block toppling for early warnings - Jian-qiao Mu; Tian-tao Li; Xiang-jun Pei; Run-qiu Huang; Fu-an Lan; Xue-qing Zou (Natural Hazards, 2022)

Gastrodin Attenuates Lipopolysaccharide-Induced Inflammatory Response and Migration via the Notch-1 Signaling Pathway in Activated Microglia - Yue-yi Yao; Run Li; Yan-ji Guo; Yu Zhao; Jia-zhi Guo; Qing-long Ai; Lian-mei Zhong; Di Lu (NeuroMolecular Medicine, 2022)

A New Species of Paradiplozoon (Monogenea: Diplozoidae), A Gill Parasite of the Schizothorax Fish (Cyprinidae: Schizothoracinae) from the Yarkand River, Xinjiang, China - Kadirden Arken; Cui-Lan Hao; Ai-Ming Guo; Wen-Run Zhang; Meng-Jie Rong; Wuljan Kamal; Sheng-Li Tian; Munira Kadir; Cheng Yue (Acta Parasitologica, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

Genesis of the Hebaoshan gold deposit in Fujian Province of Southeast China: constraints from a combined fluid inclusion, H-O-C-S-Pb-He-Ar isotope and geochronological study - Ying Ma; Shao-Yong Jiang; Hartwig E. Frimmel; Lü-Yun Zhu; Suo-Fei Xiong; Run-Sheng Chen; Xue-Xie Li (Mineralium Deposita, 2022)

The decreased expression of GW2 homologous genes contributed to the increased grain width and thousand‑grain weight in wheat-Dasypyrum villosum 6VS·6DL translocation lines - Zhiyu Feng; Long Song; Wanjun Song; Zhongqi Qi; Jun Yuan; Run Li; Haiming Han; Huifang Wang; Zhaoyan Chen; Weilong Guo; Mingming Xin; Jie Liu; et al. (Theoretical and Applied Genetics, 2021)

Different Changing Patterns of Three NOS–NO System Activities after Ischemia–Reperfusion in Rabbit with AMI - Jun Zhang; Chao Chen; Fengpeng Li; Guangren Gao; Jinguo Fu; Heping Niu; Kai Yu; Lei Wang; Run Guo; Yanfang Wan; Zhanfeng Ma; Qianyu Zhang; et al. (Cell Biochemistry and Biophysics, 2021)

An uncharacterized protein from the metagenome with no obvious homology to known lipases shows excellent alkaline lipase properties and potential applications in the detergent industry - Yue Xiao; Yi-De Liu; Ge Yuan; Run-Qian Mao; Gang Li (Biotechnology Letters, 2021)

Exploring the dynamic mechanism of allosteric drug SHP099 inhibiting SHP2E69K - Shan Du; Xin-hua Lu; Wei-Ya Li; Li-Peng Li; Yang-Chun Ma; Liang Zhou; Jing-Wei Wu; Ying Ma; Run-Ling Wang (Molecular Diversity, 2021)

Contribution of climate/meteorology to winter haze pollution in the Fenwei Plain, China - Zhijun Zhao; Shaw Chen Liu; Run Liu; Ziyin Zhang; Yanzi Li; Huisi Mo; Yanxing Wu (International Journal of Climatology, 2021)
In recent years, anthropogenic emissions in the Fenwei Plain (FWP) have decreased; however, haze pollution remains a serious issue. This study explored the possible reasons for this enduring problem in terms of climate and meteorology. Firstly, the contribution of climate and meteorology to haze pollution in the FWP was quantified using a best fit model and differences in key meteorological parameters were analysed over several time periods. Key climate factors were identified using a relative importance test and correlation analysis, and the adjusted optimal subset model (AOSM) was used to predict the number of winter haze days for the entire winter and for individual winter months, respectively. Results showed that the average minimum contribution ( CON ave ) of climate/meteorology to winter haze pollution was 24.3% from 1984 to 2016 and the modulating role of climate and meteorological conditions increased significantly after 2010 ( CON ave = 55.8%). This was attributed to a significant decrease (increase) in sea level pressure and surface wind speed (500 hPa geopotential height and surface temperature) in the FWP. The explained variance ( R 2 ) and mean absolute error (MAE) of the models for the entire winter period were 88% and 3.54 days, respectively. For predictions in November, December, January, and February, the R 2 was above 71% and the MAE was below 1.83 days. Furthermore, independent predictions for 2018 showed that the bias in the monthly models was lower by 5 days compared to the entire winter model. The results of a recycling independent test indicated that all the models evaluated had excellent stability, proving that the climate factors chosen by the AOSM do affect haze pollution in the FWP.

Genome-Wide Identification and Expression Analysis of Heavy Metal Stress–Responsive Metallothionein Family Genes in Nicotiana tabacum - Qin Yu; Linshen He; Chunsong Huo; Xiaohan Jiang; Hua Chen; Run Wang; Minzhi Tang; Ling Dong; Ji Chen; Yonghao Li; Shunqin Zhu; Wanhong Liu (Plant Molecular Biology Reporter, 2021)

Identification of differentially expressed genes associated with aluminum resistance in the soybean plant - Jing-xuan Wang; Bo Wang; Lu-bin Cui; Hao Xie; Run-zhi Li; Cheng Wang; Zhang-jie Nan; Yu-shu Liu; Jing-yu Ma; Yun-jin Sun; Wei-yu Li (Physiology and Molecular Biology of Plants, 2021)

A pair of novel bisindole alkaloid enantiomers from marine fungus Fusarium sp. XBB-9 - Sharpkate Shaker; Run-Zhu Fan; Hou-Jin Li; Wen-Jian Lan (Natural Product Research, 2021)

EPG-recorded Feeding Behaviors Reveal Adaptability and Competitiveness in Two Species of Bemisia tabaci (Hemiptera: Aleyrodidae) - Shao-hua Lu; Jing-jing Li; Run-e Bai; Feng-ming Yan (Journal of Insect Behavior, 2021)

Numerical simulation of seasonal snow in Tianshan Mountains - Yan-run Ren; Yao-nan Zhang; Jian-sheng Hao; Yong-ping Shen; Guo-hui Zhao; Cong Li (Journal of Mountain Science, 2021)

Leading modes of Asian–Australian monsoon interannual variability as represented in CMIP5 models - Fang Zhou; Hong‐Li Ren; Ming‐Hong Liu; Run Wang; Kai Huang (International Journal of Climatology, 2021)
The Asian–Australian monsoon (AAM) exerts a strong impact on the regional climate. The ability of climate models to simulate the AAM is of great importance. This study evaluates the performance of 26 models, which participate in the Coupled Model Intercomparison Project phase 5 (CMIP5), in representing features of the leading modes of the AAM interannual variability. This is achieved by diagnosing quantitative metrics derived from a Season‐reliant Empirical Orthogonal Function (S‐EOF) analysis, and plausible external forcing contributing to the simulation results are presented. Our results show that the CMIP5 models can generally capture the spatial patterns of the leading modes of AAM interannual variability during El Niño development periods because of strong air–sea interactions. The variance percentage explained by the first two S‐EOF modes is found to be closely related to the amplitude of the El Niño‐Southern Oscillation (ENSO) in the models. In contrast, simulation of the periodicity remains challenging, and the models show deficiencies in the accurate capture of periodic characteristics. Models with realistic ENSO simulations typically perform well in simulating S‐EOF1, and the key to improving the simulation of S‐EOF2 is the greater intensity of the simulated field of background heating over the Northwest Pacific warm pool. The multimodel ensemble (MME) performs better than most of the 26 individual models. Models in the MME with better ENSO simulation and stronger warm pool heating are found to be better able to represent the relationships between the first two leading S‐EOF modes and ENSO, although biases remained.

Study on NOx removal from simulated flue gas by an electrobiofilm reactor: EDTA-ferrous regeneration and biological kinetics mechanism - Nan Liu; Ying-ying Li; Du-juan Ouyang; Rui Guo; Run Chen; Wei Li; Ji-xiang Li; Ji-hong Zhao (Environmental Science and Pollution Research, 2021)

High-throughput sequencing reveals the molecular mechanisms determining the stay-green characteristic in soybeans - Cheng Wang; Le Gao; Run Zhi Li; Ye Wang; Yang Ying Liu; Xin Zhang; Hao Xie (Journal of Biosciences, 2020)

Deformation and failure of a high-steep slope induced by multi-layer coal mining - Jian-le Yu; Jian-jun Zhao; Hao-yuan Yan; Qi-yi Lai; Run-qiu Huang; Xiu-wei Liu; Yang-chnn Li (Journal of Mountain Science, 2020)

Prediction and Identification of Epitopes in the Emy162 Antigen of Echinococcus multilocularis - Ming-Quan Pang; Feng Tang; Hai-Jiu Wang; Ying Zhou; Li Ren; Run-Le Li; Hu Zhou; Chen-Fei Wan; Chuan-Chuan Liu; Cai-Rang Yangdan; Hai-Ning Fan (Acta Parasitologica, 2020)

Characterization of a Cu2+, SDS, alcohol and glucose tolerant GH1 β-glucosidase from Bacillus sp. CGMCC 1.16541 - Yi-Rui Yin; Peng Sang; Feng-Li Yang; Tao Li; Run-Feng Yang; Hong-Yan Liu; Zong-Long Luo; Wen-Jun Li; Li-Quan Yang (Antonie van Leeuwenhoek, 2020)

Inflammatory injury and mitophagy induced by Cr(VI) in chicken liver - Yue Wang; Jiajia Hao; Shuo Zhang; Liping Li; Run Wang; Yiran Zhu; Yongxia Liu; Jianzhu Liu (Environmental Science and Pollution Research, 2020)

Configuration design and correction ability evaluation of a novel external fixator for foot and ankle deformity treated by U osteotomy - Shiping Zuo; Mingjie Dong; Jianfeng Li; Chunjing Tao; Run Ji (Medical & Biological Engineering & Computing, 2020)

Physical Model Experimental Study on Spalling Failure Around a Tunnel in Synthetic Marble - Guo-Qiang Zhu; Xia-Ting Feng; Yang-Yi Zhou; Zheng-Wei Li; Lian-Jie Fu; Yong-Run Xiong (Rock Mechanics and Rock Engineering, 2020)

A Review of Research on Tropical Air-Sea Interaction, ENSO Dynamics, and ENSO Prediction in China - Hong-Li Ren; Fei Zheng; Jing-Jia Luo; Run Wang; Minghong Liu; Wenjun Zhang; Tianjun Zhou; Guangqing Zhou (Journal of Meteorological Research, 2020)

Paeoniflorin inhibits Th1 and Th17 cells in gut-associated lymphoid tissues to produce anti-arthritis activities - Fei Fei; Li-xiang Aa; Qi Qi; Run-bin Sun; Cai-xia Yan; Ji-ye Aa; Guang-ji Wang (Inflammopharmacology, 2019)

Stress-dependent anisotropy index of strength and deformability of jointed rock mass: insights from a numerical study - Na Wu; Zheng-zhao Liang; Ying-chun Li; Hong Li; Wan-run Li; Mei-li Zhang (Bulletin of Engineering Geology and the Environment, 2019)

Insights into transcriptional characteristics and homoeolog expression bias of embryo and de-embryonated kernels in developing grain through RNA-Seq and Iso-Seq - Jun Wei; Hong Cao; Jing-dong Liu; Jing-hong Zuo; Yu Fang; Chih-Ta Lin; Run-ze Sun; Wen-long Li; Yong-xiu Liu (Functional & Integrative Genomics, 2019)

Isolation and synthesis of a new benzylated alkamide from the roots of Lepidium meyenii - Yan-Qing Ye; Zu-Hong Ma; Qiao-Fen Yang; Yan-Qi Sun; Rui-Qi Zhang; Run-Fang Wu; Xin Ren; Li-Juan Mu; Zhi-Yong Jiang; Min Zhou (Natural Product Research, 2019)

Insight into the Dissolution Molecular Mechanism of Ternary Solid Dispersions by Combined Experiments and Molecular Simulations - Run Han; Tianhe Huang; Xinyang Liu; Xunqing Yin; Haifeng Li; Jiahong Lu; Yuanhui Ji; Huimin Sun; Defang Ouyang (AAPS PharmSciTech, 2019)

Effect of Interaction between Adenosine and Nitric Oxide on Central Nervous System Oxygen Toxicity - Cheng-wei Xie; Zhong-zhuang Wang; Ya-nan Zhang; Yu-liang Chen; Run-ping Li; Jun-dong Zhang (Neurotoxicity Research, 2019)

Analysis of genetic variation of porcine circovirus type 2 within pig populations in central China - Peng-Li Xu; Yu Zhao; Hui-Hua Zheng; Run-Bo Tian; Hao-Ying Han; Hong-Ying Chen; Lan-Lan Zheng (Archives of Virology, 2019)

Mechanism of toppling and deformation in hard rock slope: a case of bank slope of Hydropower Station, Qinghai Province, China - Jun-chao Cai; Neng-pan Ju; Run-qiu Huang; Da Zheng; Wei-hua Zhao; Long-qi Li; Jian Huang (Journal of Mountain Science, 2019)

Correlation between S100A11 and the TGF-β1/SMAD4 pathway and its effects on the proliferation and apoptosis of pancreatic cancer cell line PANC-1 - Yi-Fei Ji; Tao Li; Feng Jiang; Wen-Kai Ni; Cheng-Qi Guan; Zhao-Xiu Liu; Cui-Hua Lu; Run-Zhou Ni; Wei Wu; Ming-Bing Xiao (Molecular and Cellular Biochemistry, 2019)

β2-AR regulates the expression of AKR1B1 in human pancreatic cancer cells and promotes their proliferation via the ERK1/2 pathway - Ming-Bing Xiao; Dan-Dan Jin; Yu-Jie Jiao; Wen-Kai Ni; Jin-Xia Liu; Li-Shuai Qu; Cui-Hua Lu; Run-Zhou Ni; Feng Jiang; Wei-Chang Chen (Molecular Biology Reports, 2018)

The jasmonate-responsive transcription factor CbWRKY24 regulates terpenoid biosynthetic genes to promote saponin biosynthesis in Conyza blinii H. Lév. - Wen-Jun Sun; Jun-Yi Zhan; Tian-Run Zheng; Rong Sun; Tao Wang; Zi-Zhong Tang; Tong-Liang Bu; Cheng-Lei Li; Qi Wu; Hui Chen (Journal of Genetics, 2018)

Spatial patterns of interprovincial mountain geographical names in China and implications for regional governance - Sheng-rui Zhang; Ying-jie Wang; Hong-run Ju; Tong-yan Zhang; Dai-chao Li; Lei Fang; Ying-ying Wang (Journal of Mountain Science, 2018)

Rheological Behavior of Protein Hydrolysates from Papain-treated Male Gonad of Scallop ( Patinopecten yessoensis ) - Jia-Run Han; Jia-Nan Yan; Yi Li; Jun Zhao; Yue Tang; Wen-Gang Jin; Wen-Hui Shang; Meng Zhang; Hai-Tao Wu (Journal of Aquatic Food Product Technology, 2018)

Two flavonol glycosides from Liparis bootanensis - Shuai Huang; Run Wu; Feng Gao; Chunying Li; Xianli Zhou (Journal of Natural Medicines, 2018)

U–Pb zircon, geochemical and Sr–Nd–Hf isotopic constraints on age and origin of the intrusions from Wunugetushan porphyry deposit, Northeast China: implication for Triassic–Jurassic Cu–Mo mineralization in Mongolia–Erguna metallogenic belt - Kui-Feng Mi; Zhen-Jiang Liu; Rui-Bin Liu; Chun-Feng Li; Jian-Ping Wang; Run-Min Peng (International Geology Review, 2018)

Analysis of future drought characteristics in China using the regional climate model CCLM - Jinlong Huang; Jianqing Zhai; Tong Jiang; Yanjun Wang; Xiucang Li; Run Wang; Ming Xiong; Buda Su; Thomas Fischer (Climate Dynamics, 2018)

Efficient and Product-Controlled Depolymerization of Lignin Oriented by Raney Ni Cooperated with Cs x H3 − x PW12O40 - Xiao-Jun Shen; Jia-Long Wen; Pan-Li Huang; Kai Zheng; Shuang-Fei Wang; Qiu-Yun Liu; Adam Charlton; Run-Cang Sun (BioEnergy Research, 2017)

Kinetics of Antioxidant-Producing Maillard Reaction in the Mixture of Ribose and Sea Cucumber ( Stichopus japonicus ) Gut Hydrolysates - Jia-Run Han; Zhi-Mo Zhu; Hai-Tao Wu; Na Sun; Yue Tang; Cui-Ping Yu; Chen-Chen Zhao; Zheng-Yu Zhang; Ao-Ting Li; Jia-Nan Yan (Journal of Aquatic Food Product Technology, 2017)

Hydrogen Peroxide and Strigolactones Signaling Are Involved in Alleviation of Salt Stress Induced by Arbuscular Mycorrhizal Fungus in Sesbania cannabina Seedlings - Cun-Cui Kong; Cheng-Gang Ren; Run-Zhi Li; Zhi-Hong Xie; Ji-Ping Wang (Journal of Plant Growth Regulation, 2017)

Increasing the yield of middle silk gland expression system through transgenic knock-down of endogenous sericin-1 - Sanyuan Ma; Xiaojuan Xia; Yufeng Li; Le Sun; Yue Liu; Yuanyuan Liu; Xiaogang Wang; Run Shi; Jiasong Chang; Ping Zhao; Qingyou Xia (Molecular Genetics and Genomics, 2017)

Efficient yeast cell-surface display of an endoglucanase of Aspergillus flavus and functional characterization of the whole-cell enzyme - Gang Gao; Run-Qian Mao; Yue Xiao; Jing Zhou; Yu-Huan Liu; Gang Li (World Journal of Microbiology and Biotechnology, 2017)

Phytochemicals and biological activities of Artemisia sieversiana - Shi-Jun Liu; Zhi-Xin Liao; Zhi-Shu Tang; Chun-Li Cui; Hong-Bo Liu; Yan-Ni Liang; Yu Zhang; Huan-Xian Shi; Yao-Run Liu (Phytochemistry Reviews, 2017)

Effect of rainfall on a colluvial landslide in a debris flow valley - Liang Qiao; Xing-min Meng; Guan Chen; Yi Zhang; Peng Guo; Run-qiang Zeng; Ya-jun Li (Journal of Mountain Science, 2017)

Evaluation of the antioxidant property and effects in Caenorhabditis elegans of Xiangxi flavor vinegar, a Hunan local traditional vinegar - Run-ting Huang; Qing Huang; Gen-liang Wu; Chun-guang Chen; Zong-jun Li (Journal of Zhejiang University-SCIENCE B, 2017)

Upper-ocean dynamical features and prediction of the super El Niño in 2015/16: A comparison with the cases in 1982/83 and 1997/98 - Hong-Li Ren; Run Wang; Panmao Zhai; Yihui Ding; Bo Lu (Journal of Meteorological Research, 2017)

Identification and characterization of multiple porcine astrovirus genotypes in Hunan province, China - Chao-Ting Xiao; Zhang Luo; Sun-Liang Lv; Tanja Opriessnig; Run-Cheng Li; Xing-Long Yu (Archives of Virology, 2017)

Inhibitory effect of estrogen receptor beta on P2X3 receptors during inflammation in rats - Qian Jiang; Wen-xin Li; Jia-run Sun; Tian-tian Zhu; Juan Fan; Li-hua Yu; Geoffrey Burnstock; Hua Yang; Bei Ma (Purinergic Signalling, 2017)

Skarn mineralogy and its geological significance for the Tayuan (Cu–Mo)–Pb–Zn deposit, northern Daxinganling metallogenic belt - Chao Li; Tao Ren; Jian-Guo Huang; Run-Sheng Han; He-Jun Yin; Hong-Yang Zhou; Zhi-Hong Feng (Acta Geochimica, 2017)

Phylogeography of Achyranthes bidentata (Amaranthaceae) in China’s Warm-Temperate Zone Inferred from Chloroplast and Nuclear DNA: Insights into Population Dynamics in Response to Climate Change During the Pleistocene - Cai-Yun Miao; Jie Yang; Run-Li Mao; Yong Li (Plant Molecular Biology Reporter, 2017)

Population structure and diversity of citrus tristeza virus (CTV) isolates in Hunan province, China - Cui Xiao; Run-Xian Yao; Fang Li; Su-Ming Dai; Grazia Licciardello; Antonino Catara; Alessandra Gentile; Zi-Niu Deng (Archives of Virology, 2017)

Gastroprotective effect of palmatine against acetic acid-induced gastric ulcers in rats - Ling Wang; Xue Wang; Su-Li Zhang; Xiao-Ming Zhu; Yan-Qi Liu; Zi-Jing Song; Wen-Juan Du; Jun Ji; Cheng-Long Cui; Xin He; Chun-Feng Zhang; Chang-Run Guo; et al. (Journal of Natural Medicines, 2017)

Spatiotemporal distributions of influential tropical cyclones and associated economic losses in China in 1984–2015 - Yanjun Wang; Shanshan Wen; Xiucang Li; Fischer Thomas; Buda Su; Run Wang; Tong Jiang (Natural Hazards, 2016)

A new coumarin isolated from Sarcandra glabra as potential anti-inflammatory agent - Maojie Wang; Jin Zhao; Ya Zhao; Run-Yue Huang; Geng Li; Xing Zeng; Xiong Li (Natural Product Research, 2016)

Transcriptome analysis reveals translational regulation in barley microspore-derived embryogenic callus under salt stress - Cheng-hong Liu; Rui-ju Lu; Gui-mei Guo; Ting He; Ying-bo Li; Hong-wei Xu; Run-hong Gao; Zhi-wei Chen; Jian-hua Huang (Plant Cell Reports, 2016)

Variability in rainfall threshold for debris flow after Wenchuan earthquake in Gaochuan River watershed, Southwest China - Tian-Tao Li; Run-Qiu Huang; Xiang-Jun Pei (Natural Hazards, 2016)

Silencing of HMGA2 promotes apoptosis and inhibits migration and invasion of prostate cancer cells - Zhan Shi; Ding Wu; Run Tang; Xiang Li; Renfu Chen; Song Xue; Chengjing Zhang; Xiaoqing Sun (Journal of Biosciences, 2016)

The formation and evolution of the Qiaojia pull-apart basin, North Xiaojiang Fault Zone, Southwest China - Tian-tao Li; Xiang-jun Pei; Run-qiu Huang; Long-de Jin (Journal of Mountain Science, 2016)

Influence of the characteristics of fault gouge on the stability of a borehole wall - Sheng Wang; Li-yi Chen; Run-qiu Huang; Zhi-jun Li; Jin-sheng Wu; Chao-peng Yuan (Journal of Mountain Science, 2016)

A Brachypodium distachyon MAPKK Gene BdMKK6.2 Negatively Regulates Drought Stress Tolerance in Transgenic Tobacco Plants - Jiutong Sun; Run Zhou; Yaping Li; Wei Hu; Ding Qiu; Xiatian Wang; Qiong Wang; Zhijuan Feng; Lianzhe Wang; Yi Zhou; Guangyuan He; Guangxiao Yang (Journal of Plant Growth Regulation, 2016)

Identification and mapping of Tril, a homeodomain-leucine zipper gene involved in multicellular trichome initiation in Cucumis sativus - Yun-Li Wang; Jing-tao Nie; Hui-Ming Chen; Chun-li Guo; Jian Pan; Huan-Le He; Jun-Song Pan; Run Cai (Theoretical and Applied Genetics, 2016)

Trends of regional precipitation and their control mechanisms during 1979–2013 - Run Liu; Shaw Chen Liu; Chein-Jung Shiu; Jun Li; Yuanhang Zhang (Advances in Atmospheric Sciences, 2016)

Transcriptome profiling of trichome-less reveals genes associated with multicellular trichome development in Cucumis sativus - Jun-Long Zhao; Yun-Li Wang; Dan-Qing Yao; Wen-Ying Zhu; Long Chen; Huan-Le He; Jun-Song Pan; Run Cai (Molecular Genetics and Genomics, 2015)

Response to comments by Yuan Wang on “Trends of extreme precipitation in Eastern China and their possible causes” - Run Liu; Shaw Chen Liu; Ralph J. Cicerone; Chein-Jung Shiu; Jun Li; Jingli Wang; Yuanhang Zhang (Advances in Atmospheric Sciences, 2015)

A Real-time monitoring and early warning system for landslides in Southwest China - Neng-pan Ju; Jian Huang; Run-qiu Huang; Chao-yang He; Yan-rong Li (Journal of Mountain Science, 2015)

Sediment delivery across multiple spatio-temporal scales in an agriculture watershed of the Chinese Loess Plateau - Ming-guo Zheng; Run-kui Li; Ji-jun He; Ming Cui (Journal of Mountain Science, 2015)

Trends of extreme precipitation in eastern China and their possible causes - Run Liu; Shaw Chen Liu; Ralph J. Cicerone; Chein-Jung Shiu; Jun Li; Jingli Wang; Yuanhang Zhang (Advances in Atmospheric Sciences, 2015)

The Brachypodium distachyon BdWRKY36 gene confers tolerance to drought stress in transgenic tobacco plants - Jiutong Sun; Wei Hu; Run Zhou; Lianzhe Wang; Xiatian Wang; Qiong Wang; Zhijuan Feng; Yaping Li; Ding Qiu; Guangyuan He; Guangxiao Yang (Plant Cell Reports, 2015)

A convenient four-component one-pot synthesis of 2-amino-1,3,4-thiadiazoles in water - Peng Liu; Ao-Ze Su; Yuan-Qiang Wang; Ze-Mei Ge; Tie-Ming Cheng; Run-Tao Li (Molecular Diversity, 2014)

Spatial differentiation of tourism impact based on the perception of residents in mountainous valley resorts - Shan-shi Li; Jia-ming Liu; Run Wang; He Zhu (Journal of Mountain Science, 2014)

Evolution of High-Affinity Peptide Probes to Detect the SH3 Domain of Cancer Biomarker BCR–ABL - Hui-Min Liu; Li-Juan Li; Juan Guo; Zhan-Jia Yang; Xiao Yang; Run-Peng Qi; Wei Cao (International Journal of Peptide Research and Therapeutics, 2014)

High seroprevalence of Chlamydia infection in sows in Hunan province, subtropical China - Xiao-Xuan Zhang; Run-Cheng Li; Guo-Hua Liu; Wei Cong; Hui-Qun Song; Xing-Long Yu; Xing-Quan Zhu (Tropical Animal Health and Production, 2014)

Fine mapping of the uniform immature fruit color gene u in cucumber (Cucumis sativus L.) - Xuqin Yang; Yue Li; Weiwei Zhang; Huanle He; Junsong Pan; Run Cai (Euphytica, 2014)

Phenotypic and genetic parameter estimation of morphological traits related to axial body growth in Japanese flounder - Yong-Xin Liu; Li Jiang; Hai-Jin Liu; Run-Qing Yang (Fisheries Science, 2014)

The influence of nitrogen on the development and accumulation of protein bodies in the developing endosperm of wheat caryopses - Fei Xiong; Xu-Run Yu; Liang Zhou; Jing Zhang; Bo Li; Jian Liu; Feng Wang; Ai-Sheng Xiong (Molecular Biology Reports, 2014)

Rapid susceptibility mapping of co-seismic landslides triggered by the 2013 Lushan Earthquake using the regression model developed for the 2008 Wenchuan Earthquake - Wei-le Li; Run-qiu Huang; Qiang Xu; Chuan Tang (Journal of Mountain Science, 2013)

Treatment of Furfural Residue by Solvent Extraction for Enzymatic Hydrolysis: Effect of Delignification on the Structure and Digestibility - Shao-Ni Sun; Xue-Fei Cao; Ming-Fei Li; Feng Xu; Run-Cang Sun (BioEnergy Research, 2013)

Engineering geological assessment for route selection of railway line in geologically active area: A case study in China - Run-qiu Huang; Yan-rong Li; Ke Qu; Ke Wang (Journal of Mountain Science, 2013)
The Cheng-Lan railway links Chengdu, a central city in Southwestern China, and Lanzhou, a central city in Northwestern China. The railway passes through the Longmenshan fault zone (Wenchuan earthquake happened there on May 12, 2008), Minjiang fault zone, and Dongkunlun fault zone, which are all active. It runs over the Yangtze River and the Yellow River, and crosses high mountains and deep valleys. There exists, along the railway’s alignment, different kinds of strata of hard granite and soft, weak metamorphic rocks such as carbonaceous slate, schist, and phyllite. It is, therefore, a key issue for such an infrastructure construction to assess the engineering geological conditions and risks, so as to mitigate or avoid possible georisks and to offer optional designs. Geological survey and georisk assessment along the railway corridor are carried out. Special attention is given to active faults, earthquakes and seismic zones. Based on these, discussions about geological aspects for route selection of the railway are conducted and countermeasures for georisk control are proposed accordingly. Main conclusions are achieved as follows: (1) Geohazards such as landslides, rockfalls and debries flows dominate both the route selection of the railway and the engineering structures (e.g., tunnels or bridges) adopted; (2) Tunnel has been proved to be an excellent structure for linear engineering in geologically active area; and (3) In the case where avoiding is impractical, necessary protection measures should be taken to engineering slopes in high earthquake intensity areas, especially the area with earthquake of Ms. 8 or greater.

Progressive modelling of the gravity-induced landslide using the local dynamic strength reduction method - Guo-qing Chen; Run-qiu Huang; Qiang Xu; Tian-bin Li; Ming-lei Zhu (Journal of Mountain Science, 2013)
The failure of slope is a progressive process, and the whole sliding surface is caused by the gradual softening of soil strength of the potential sliding surface. From this viewpoint, a local dynamic strength reduction method is proposed to capture the progressive failure of slope. This method can calculate the warning deformation of landslide in this study. Only strength parameters of the yielded zone of landslide will be reduced by using the method. Through continuous local reduction of the strength parameters of the yielded zone, the potential sliding surface developed gradually and evolved to breakthrough finally. The result shows that the proposed method can simulate the progressive failure of slope truly. The yielded zone and deformation of landslide obtained by the method are smaller than those of overall strength reduction method. The warning deformation of landslide can be obtained by using the local dynamic strength reduction method which is based on the softening characteristics of the sliding surface.

Expression of yeast acyl-CoA-∆9 desaturase leads to accumulation of unusual monounsaturated fatty acids in soybean seeds - Jin-Ai Xue; Xue Mao; Zhi-Rong Yang; Yong-Mei Wu; Xiao-Yun Jia; Li Zhang; Ai-Qin Yue; Ji-Ping Wang; Run-Zhi Li (Biotechnology Letters, 2013)

Co-seismic landslide inventory and susceptibility mapping in the 2008 Wenchuan earthquake disaster area, China - Wei-le Li; Run-qiu Huang; Chuan Tang; Qiang Xu; Cees van Westen (Journal of Mountain Science, 2013)

Permeability and sedimentation characteristics of pleistocene fluvio-glacial deposits in the Dadu river valley, Southwest China - Guo-xiang Tu; Run-qiu Huang; Hui Deng; Yan-rong Li (Journal of Mountain Science, 2013)

Effect of Zinc Source on Performance, Zinc Status, Immune Response, and Rumen Fermentation of Lactating Cows - Run L. Wang; Jian G. Liang; Lin Lu; Li Y. Zhang; Su F. Li; Xu G. Luo (Biological Trace Element Research, 2013)

Acute Clenbuterol Induces Hypotension, Atrioventricular Block and Cardiac Asystole in the Rabbit - Yan Ke; Li-Lan Fu; Xia-Fei Hong; Run Dong; Tian-Ming Xu; Jing-Fei Guo; Yan Liu; Ji-Min Cao (Cardiovascular Toxicology, 2013)

Selective pressure dominates the synonymous codon usage in parvoviridae - Sheng-Lin Shi; Yi-Ren Jiang; Yan-Qun Liu; Run-Xi Xia; Li Qin (Virus Genes, 2013)

RT-PCR test for detecting porcine sapovirus in weanling piglets in Hunan Province, China - Guo-Hua Liu; Run-Cheng Li; Ze-Bin Huang; Jun Yang; Chao-Ting Xiao; Jing Li; Man-Xiang Li; Yun-Qiu Yan; Xing-Long Yu (Tropical Animal Health and Production, 2012)

Evaluation of the predatory mite Amblyseius hainanensis (Acari: Phytoseiidae) and artificial rainfall for the management of Brevipalpus obovatus (Acari: Tenuipalpidae) - Da-Rui Zheng; Guang-Hua Liu; Run-Jie Zhang; Andrew G. S. Cuthbertson; Bao-Li Qiu (Experimental and Applied Acarology, 2012)

An efficient three-component, one-pot synthesis of 2-alkylthio-4-amino-5-cyano-6-aryl(alkyl)pyrimidines in water - Qiao-Yan Li; Ze-Mei Ge; Tie-Ming Cheng; Run-Tao Li (Molecular Diversity, 2012)

Seroprevalence of porcine cytomegalovirus and sapovirus infection in pigs in Hunan province, China - Guo-Hua Liu; Run-Cheng Li; Jing Li; Ze-Bin Huang; Chao-Ting Xiao; Wei Luo; Meng Ge; Da-Liang Jiang; Xing-Long Yu (Archives of Virology, 2012)

Construction of a high density integrated genetic map for cucumber (Cucumis sativus L.) - Wei-Wei Zhang; Jun-Song Pan; Huan-Le He; Chi Zhang; Zheng Li; Jun-Long Zhao; Xiao-Jun Yuan; Li-Huang Zhu; San-Wen Huang; Run Cai (Theoretical and Applied Genetics, 2012)

Effects of exogenous hydrogen sulfide on the ascorbate and glutathione metabolism in wheat seedlings leaves under water stress - Chang-juan Shan; Sheng-li Zhang; Dong-fang Li; Yuan-zeng Zhao; Xue-liang Tian; Xin-liang Zhao; Ying-xia Wu; Xiu-ying Wei; Run-qiang Liu (Acta Physiologiae Plantarum, 2011)

Effects of temporarily disrupting BBB on activity-induced manganese-dependent functional MRI - Zhiqiang Fa; Run Zhang; Peng Li; Jing Zhang; Peng Zhang; Shaofang Zhu; Qu Wu; Fanheng Huang; Yanping Liu; Lujun Yang; Haigang Chang; Zhibo Wen; et al. (Brain Imaging and Behavior, 2011)

Comparative ecophysiological responses to drought of two shrub and four tree species from karst habitats of southwestern China - Chang-Cheng Liu; Yu-Guo Liu; Ke Guo; Guo-Qing Li; Yuan-Run Zheng; Li-Fei Yu; Rui Yang (Trees, 2011)

Expression patterns of prion protein gene in differential genotypes sheep: quantification using molecular beacon real-time RT-PCR - Chuan Wang; Run Wu; Fa-Di Li; Lei Liu; Xiao-Li Zhang; Chun-Lin Zhao; Xiao-Long Diao; Hong-Wei Guan (Virus Genes, 2011)

Screening Level of PAHs in Sediment Core from Lake Hongfeng, Southwest China - Jian-Yang Guo; Feng-Chang Wu; Liang Zhang; Hai-Qing Liao; Run-Yu Zhang; Wei Li; Xiao-Li Zhao; She-Jun Chen; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2011)

RRM1 gene expression in peripheral blood is predictive of shorter survival in Chinese patients with advanced non-small-cell lung cancer treated by gemcitabine and platinum - Lin-run Wang; Guo-bing Zhang; Jian Chen; Jun Li; Ming-wei Li; Nong Xu; Yang Wang; Jian-zhong Shen Tu (Journal of Zhejiang University-SCIENCE B, 2011)

Targeted killing effects of double CD and TK suicide genes controlled by survivin promoter on gastric cancer cell - Xian-Run Luo; Jian-Sheng Li; Ying Niu; Li Miao (Molecular Biology Reports, 2011)

The Cucumber Lateral Suppressor Gene (CLS) Is Functionally Associated with Axillary Meristem Initiation - Li-Hua Yuan; Jun-Song Pan; Gang Wang; Jun Zhu; Wei-Wei Zhang; Zheng Li; Huan-Le He; Zhong-Nan Yang; Run Cai; Li-Huang Zhu (Plant Molecular Biology Reporter, 2010)

Identification and mapping of molecular markers linked to the tuberculate fruit gene in the cucumber (Cucumis sativus L.) - Weiwei Zhang; Huanle He; Yuan Guan; Hui Du; Lihua Yuan; Zheng Li; Danqing Yao; Junsong Pan; Run Cai (Theoretical and Applied Genetics, 2010)

Effects of exogenous putrescine on gas-exchange characteristics and chlorophyll fluorescence of NaCl-stressed cucumber seedlings - Run Hua Zhang; Jun Li; Shi Rong Guo; Takafumi Tezuka (Photosynthesis Research, 2009)

Two new flavanone glycosides from Veratrum nigrum L. - Hui-Liang Li; Jian Tang; Run-Hui Liu; Chuan Zhang; Wei-Dong Zhang (Natural Product Research, 2009)

Molecular interaction between prion protein and GFAP both in native and recombinant forms in vitro - Chen-Fang Dong; Xiao-Fan Wang; Xin Wang; Song Shi; Gui-Rong Wang; Bing Shan; Run An; Xiao-Li Li; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2008)

Development and fine mapping of three co-dominant SCAR markers linked to the M/m gene in the cucumber plant (Cucumis sativus L.) - Zheng Li; Junsong Pan; Yuan Guan; Qianyi Tao; Huanle He; Longting Si; Run Cai (Theoretical and Applied Genetics, 2008)

Repair of glutamate-induced excitotoxic neuronal damage mediated by intracerebroventricular transplantation of neural stem cells in adult mice - Juan Ma; Li-Jian Yu; Run-Di Ma; Yong-Ping Zhang; Juan-Zhi Fang; Xiao-Yu Zhang; Ting-Xi Yu (Neuroscience Bulletin, 2007)

Characterizations of a Hypomorphic Argonaute1 Mutant Reveal Novel AGO1 Functions in Arabidopsis Lateral Organ Development - Li Yang; Weihua Huang; Hua Wang; Run Cai; Yuquan Xu; Hai Huang (Plant Molecular Biology, 2006)

Testifying the rice bacterial blight resistance gene xa5 by genetic complementation and further analyzing xa5 (Xa5) in comparison with its homolog TFIIAγ1 - Guang-Huai Jiang; Zhi-Hui Xia; Yong-Li Zhou; Jia Wan; Da-Yong Li; Run-Sheng Chen; Wen-Xue Zhai; Li-Huang Zhu (Molecular Genetics and Genomics, 2006)